Integrating climate adaptation and peacebuilding: capacity development in climate and conflict-affected communities - Luisa Fernanda Bedoya Taborda; Tiffany H. Morrison; Michele L. Barnes (Global Environmental Change, 2026)

Adaptive area-wide management for suppressing spruce budworm outbreaks: effectiveness of the early intervention strategy - Rob C. Johns; S. Edwards; L. Amos-Binks; J. J. Bowden; D. Carleton; C. Edge; C. Hennigar; P. James; D. MacLean; V. Martel; E. R. D. Moise; B. Morin; et al. (Journal of Pest Science, 2026)
In eastern North America, two main insecticide-based strategies are used to manage spruce budworm ( Choristoneura fumiferana ) outbreaks. The traditional ‘Foliage Protection Strategy’ (FPS) focuses on temporarily reducing defoliation and tree mortality in high-value stands, allowing outbreaks to progress naturally in surrounding areas. The ‘Early Intervention Strategy’ (EIS) is an adaptive, area-wide management approach that targets low-density “hotspots” to prevent outbreak growth and spread. We report findings from a 10-year case study (2015–2024) in Atlantic Canada assessing EIS effectiveness. EIS treatments consistently reduced population growth rates, resulting in a 12–67% reduction in hotspot areas compared to untreated areas. Crucially, this suppression curbed the rise and spread of the outbreak across northern New Brunswick, with negligible defoliation observed throughout the study period. By comparison, in a neighboring Quebec study area contemporaneously managed with FPS, the outbreak advanced normally, causing moderate to severe defoliation over ~ 1.7 million hectares by 2024. Moreover, EIS required ~ 80% less insecticide, with 66% of treated areas receiving treatment in only a single year, compared with just 15% under FPS. Our findings provide robust evidence for the effectiveness of EIS when implemented under suitable conditions, highlighting its potential as a proactive outbreak management approach.

Cellulosic biorefinery siting and biomass supply logistics incorporating biomass and moisture dynamics in the crop season and during storage - Yubin Yang; Lloyd T. Wilson; Jing Wang; Fugen Dou; Tanumoy Bera; Joseph E. Knoll; John L. Jifon; Dennis C. Odero; Brian S. Baldwin; William L. Rooney; Hamid Araji; Jesse I. Morrison; et al. (Biomass and Bioenergy, 2026)

Finding the Best Nursery: How Habitat Features Shape Juvenile Snapper ( Chrysophrys auratus ) Density - Jessica L. Campbell; Richard B. Taylor; Mark A. Morrison (New Zealand Journal of Marine and Freshwater Research, 2026)
This study examines habitat preferences of juvenile Australasian snapper ( Chrysophrys auratus ) in northeastern New Zealand, analysing data from 113 stations across structured and unstructured habitats. We investigated how juvenile snapper densities were influenced by environmental factors, including prey availability and physical habitat features. Seagrass supported significantly higher snapper densities than all other habitats, with mean densities more than 80 times greater than non‐seagrass habitats, reinforcing its role as a key nursery habitat. Regression analyses identified seagrass presence as the strongest predictor of density, with benthic productivity and plankton flux also weakly correlated when considering all habitats together. In non‐seagrass environments, there were weak trends for densities to be higher in shallow water and in the presence of burrows. Current speed also appeared to play a role, potentially modifying prey availability and interacting with habitat structure. These findings provide new insights into why seagrass meadows are particularly beneficial for juvenile snapper, reinforcing the need for targeted conservation and restoration efforts to sustain nursery habitats and support snapper populations.

Seagrass Gains: Faster Growth, Better Condition, Less Effort for Juvenile Snapper ( Chrysophrys auratus ) - Jessica L. Campbell; Christine Stewart; Mark A. Morrison (New Zealand Journal of Marine and Freshwater Research, 2026)
Seagrass habitats are widely recognised as key nursery areas for juvenile fish, yet their specific role in supporting growth and condition remains incompletely understood. This study investigates the diet, growth and condition of juvenile (0+) snapper ( Chrysophrys auratus ) across multiple habitats in the Hauraki Gulf and northeastern New Zealand, with a focus on seagrass meadows. A total of 416 snapper were analysed for condition and growth, while diet composition was assessed from 425 gut samples. Results indicate that snapper within seagrass habitats exhibited significantly higher condition and faster growth rates than those in other habitats. However, contrary to expectations, gut fullness was lower in seagrass beds than in non‐seagrass habitats, despite higher prey availability in seagrass meadows. While diet varied among habitat types, no significant differences were detected between seagrass and non‐seagrass habitats. These findings suggest that the advantages conferred by seagrass are not directly linked to food intake but may result from reduced energetic costs associated with shelter from currents, improved foraging efficiency, or lower predation stress. The study highlights the vital role of seagrass meadows in supporting juvenile snapper populations and emphasises the need for conservation and restoration, particularly in areas where these habitats have been lost.

Distinguishing natural from mining-related metal sources by including streambank groundwater data in a stream mass loading study - Andrew H. Manning; Robert L. Runkel; Jean M. Morrison; Sara Warix; Richard B. Wanty; Katherine Walton-Day; Michael Snook (Journal of Contaminant Hydrology, 2026)

Population genetics of the endangered narrowly endemic Island Marble butterfly (Euchloe ausonides insulanus) - Kara S. Jones; Aaron W. Aunins; Colleen C. Young; Robin L. Johnson; Cheryl L. Morrison (Conservation Genetics, 2026)

Shallow estuarine reef as nursery habitat for Australasian snapper ( Chrysophrys auratus ) - Jessica L. Campbell; Mark A. Morrison; Richard B. Taylor (New Zealand Journal of Marine and Freshwater Research, 2025)
Estuaries are important recruitment sites for many fish species, with structurally‐complex habitats such as subtidal seagrass beds on soft sediments particularly valuable due to their provision of food and shelter. Soft sediments dominate most estuaries, but where hard‐bottom reefs are present they have the potential to act as nursery habitats for juvenile fish. We document recruitment of juvenile Australasian snapper ( Chrysophrys auratus ) to a shallow linear sandstone reef in Whangateau Harbour, a small estuary in north‐eastern New Zealand. Up to several hundred 0 + juveniles (∼20–70 mm fork length) were present on the reef during early summer to mid‐late autumn each year from 2018 to 2021. Numbers were consistently highest at the seaward end of the reef, facing into incoming tidal currents, and lowest in the deeper central part of the reef, where larger, potentially cannibalistic, snapper were common. Juveniles disappeared from the reef fairly abruptly at the end of each season, with departure in at least two of the years appearing to follow a sudden decrease in water temperature rather than being associated with body size or absolute temperature. Although relatively small in area, estuarine reefs may be increasingly important nursery habitats in the future given the widespread loss of subtidal seagrass beds.

Proximity, politics, and preferences: Spatial and contextual patterns in management opinions for an imperiled multifunctional landscape - Haley K. Netherton-Morrison; Matthew A. Williamson; Morey Burnham; Rebecca L. Som Castellano; Kelly A. Hopping (Land Use Policy, 2025)

The U.S. Ecosystem‐Based Fisheries Management Policy and Road Map: Assessing Progress and Applying Lessons Learned - Chris J. Harvey; Yvonne L. deReynier; Wendy E. Morrison; Jennifer L. Cudney; Dorothy M. Dick; Travis Ford; Karla Gore; Jamison M. Gove; Elliott L. Hazen; Jerome M. Hermsen; Keith Kamikawa; Mandy Karnauskas; et al. (Fish and Fisheries, 2025)
The need for ecosystem‐based fisheries management (EBFM) is growing more urgent as environmental changes, species shifts, new ocean uses, and other factors force oceans toward novel states. In the United States, the National Oceanic and Atmospheric Administration's National Marine Fisheries Service (NOAA Fisheries) developed an EBFM Policy in 2016, accompanied by a Road Map of 49 action items, to support marine ecosystem‐based management and conservation of fisheries, habitats, and protected species under U.S. federal jurisdiction. In 2024, NOAA Fisheries updated its EBFM Policy and Road Map and formed a team of science and policy experts to review progress and derive lessons learned during the first Road Map iteration. Four key lessons emerged: (1) progress toward EBFM in the U.S. has been substantial; (2) greater coordination could further enhance progress; (3) more effort is required to link science to management activities; and (4) human dimensions need greater integration throughout EBFM implementation. Enabling factors for progress on the Road Map included: champions at both the leadership and staff levels; use of participatory processes; motivation driven by ecosystem shocks and threats; and leveraging existing processes and frameworks. The updated EBFM Road Map supports historic and ongoing efforts to implement U.S. laws through improved coordination, integration, and knowledge exchange and can help to address many urgent challenges facing U.S. marine fisheries, habitats, and protected resources.

Metrics of Urbanicity and Rurality in US-Based Epidemiologic Studies of Ambient Temperature and Health: A Scoping Review - Nicholaus P. Johnson; Alexandra Del Favero-Campbell; Amruta Nori-Sarma; Audrey Amezcua-Smith; Brandon Lewis; Chen Chen; Chengyi Lin; Damien Foo; Garam Byun; Hayon Michelle Choi; Honghyok Kim; Jesse D. Berman; et al. (Current Environmental Health Reports, 2025)

Clarifying the role of the resist–accept–direct framework in supporting resource management planning processes - Gregor W. Schuurman; Wylie Carr; Cat Hawkins Hoffman; David J. Lawrence; Brian W. Miller; Erik A. Beever; Jean Brennan; Katherine R. Clifford; Scott Covington; Shelley D. Crausbay; Amanda E. Cravens; John Gross; et al. (Conservation Biology, 2025)

The impacts of pesticide exposure on fish conspecific interactions: A systematic review and meta-analysis - Kyle Morrison; Gabriel Melhado; Aneesh P.H. Bose; Rhiannon Eastment; Malgorzata Lagisz; Jack L. Manera; Marcus Michelangeli; Shiho Ozeki; Bob B.M. Wong; Yefeng Yang; Shinichi Nakagawa (Environmental Pollution, 2025)

Genomics and serotyping of Tenacibaculum maritimum outbreak isolates from Australia and New Zealand for guided vaccine development and stewardship - O. Rudenko; C. Angelucci; K. Kumanan; L. Delisle; J. Carson; R.N. Morrison; K.S. Hutson; A.C. Barnes (Aquaculture, 2025)

Quantifying the influence of climate change on pesticide risks in drinking water - J. Harmon O'Driscoll; M.G. Healy; A. Siggins; J. McGinley; E. O'Brien; J. Wang; P. Holloway; P.-E. Mellander; L. Morrison; S. Scannell; P.C. Ryan (Science of The Total Environment, 2025)

Nuance in the Narrative of a Brown Poison Frog: Environmental Alkaloids and Specialized Foraging in a Presumed Toxin-Free and Diet-Generalized Species - Jeffrey L. Coleman; Steven Y. Wang; Paul E. Marek; Colin R. Morrison; Brian E. Sedio; David C. Cannatella (Journal of Chemical Ecology, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Overcoming lock-in of science-policy responses to reef heating - Tiffany H. Morrison; Jon Barnett; Georgina G. Gurney; Jacqueline Lau; Michele L. Barnes; Josh Cinner; Missaka Hettiarachchi; Pip Cohen (Marine Policy, 2024)

Nitrous oxide and methane fluxes from plasma-treated pig slurry applied to winter wheat - I. L. Lloyd; R. P. Grayson; M. V. Galdos; R. Morrison; P. J. Chapman (Nutrient Cycling in Agroecosystems, 2024)
The use of livestock waste as an organic fertiliser releases significant greenhouse gas emissions, exacerbating climate change. Innovative fertiliser management practices, such as treating slurry with plasma induction, have the potential to reduce losses of carbon and nitrogen to the environment. The existing research on the effectiveness of plasma-treated slurry at reducing nitrous oxide (N 2 O) and methane (CH 4 ) emissions, however, is not comprehensive, although must be understood if this technology is to be utilised on a large scale. A randomised block experiment was conducted to measure soil fluxes of N 2 O and CH 4 from winter wheat every two hours over an 83-day period using automated chambers. Three treatments receiving a similar amount of plant-available N were used: (1) inorganic fertiliser (IF); (2) pig slurry combined with inorganic fertiliser (PS); (3) plasma-treated pig slurry combined with inorganic fertiliser (TPS). Cumulative N 2 O fluxes from TPS (1.14 g N m −2 ) were greater than those from PS (0.32 g N m −2 ) and IF (0.13 g N m −2 ). A diurnal pattern in N 2 O fluxes was observed towards the end of the experiment for all treatments, and was driven by increases in water-filled pore space and photosynthetically active radiation and decreases in air temperature. Cumulative CH 4 fluxes from PS (3.2 g C m −2 ) were considerably greater than those from IF (− 1.4 g C m −2 ) and TPS (− 1.4 g C m −2 ). The greenhouse gas intensity of TPS (0.2 g CO 2 -eq kg grain −1 ) was over twice that of PS (0.07 g CO 2 -eq kg grain −1 ) and around six times that of IF (0.03 g CO 2 -eq kg grain −1 ). Although treating pig slurry with plasma induction considerably reduced CH 4 fluxes from soil, it increased N 2 O emissions, resulting in higher non-CO 2 emissions from this treatment. Life-cycle analysis will be required to evaluate whether the upstream manufacturing and transport emissions associated with inorganic fertiliser usage are outweighed by the emissions observed following the application of treated pig slurry to soil.

In situ allelopathic expression by the invasive amphibious plant, Ludwigia hexapetala (water primrose) across habitat types, seasons, and salinities - Judith Z. Drexler; Michael Gross; Michelle L. Hladik; Bailey Morrison; Erin Hestir (Biological Invasions, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Small-scale fluidised bed flotation device for ore amenability testing - I. Verster; B. Awatey; L. Forbes; A. Morrison; M. Mankosa; K. Runge (Minerals Engineering, 2024)

Community engagement and power dynamics in conservation philanthropy grant making - Michele M. Betsill; Rebecca L. Gruby; Jeffrey Blackwatters; Ash Enrici; Elodie Le Cornu; Xavier Basurto; Chad English; Charlotte Hudson; Leah Meth; Imani Fairweather‐Morrison; Dana Okano; David Secord (Conservation Biology, 2024)
Funding decisions influence where, how, and by whom conservation is pursued globally. In the context of growing calls for more participatory, Indigenous‐led, and socially just conservation, we undertook the first empirical investigation of how philanthropic foundations working in marine conservation globally engage communities in grant‐making decisions. We paid particular attention to whether and how community engagement practices reinforce or disrupt existing power dynamics. We conducted semistructured remote interviews with 46 individuals from 32 marine conservation foundations to identify how conservation foundations engage communities in setting their priorities and deciding which organizations and projects to fund. We found that community engagement in foundation decision‐making was limited in practice. Eleven of the 32 foundations reported some form of community engagement in funding decisions. Two of these foundations empowered communities to shape funding priorities and projects through strong forms of engagement. Many engagement practices were one way, one time, or indirect and confined to certain points in decision‐making processes. These weaker practices limited community input and reinforced unequal power relations, which may undermine the legitimacy, equity, and effectiveness of conservation efforts. We suggest that foundations aim for stronger forms of community engagement and reflect on how their grant‐making practices affect power relations between foundations and communities.

Stochastic modelling of pesticide transport to drinking water sources via runoff and resulting human health risk assessment - J. Harmon O'Driscoll; J. McGinley; M.G. Healy; A. Siggins; P.-E. Mellander; L. Morrison; E. Gunnigle; P.C. Ryan (Science of The Total Environment, 2024)

Structured decision making remains underused in ecological restoration despite opportunities - Morgan L. Piczak; Jessica A. Robichaud; Peter Morrison; Andrew M. Rous; Ingeborg M. Mulder; Cassandra J. Hill; Tanya S. Prystay; Hanna Rosner-Katz; Kelly F. Robinson; Joseph R. Bennett; Steven J. Cooke (Environment Systems and Decisions, 2024)

How long have we been mistaken? Multi-tools shedding light into the systematics of the widespread deep-water genus Madrepora Linnaeus, 1758 (Scleractinia) - Kátia C.C. Capel; Carla Zilberberg; Raphael M. Carpes; Cheryl L. Morrison; Claudia F. Vaga; Andrea M. Quattrini; Randolph ZB Quek; Danwei Huang; Stephen D. Cairns; Marcelo V. Kitahara (Molecular Phylogenetics and Evolution, 2024)

The Cerebellar Cognitive Affective/Schmahmann Syndrome Scale in Spinocerebellar Ataxias - Louisa P. Selvadurai; Susan L. Perlman; Tetsuo Ashizawa; George R. Wilmot; Chiadi U. Onyike; Liana S. Rosenthal; Vikram G. Shakkottai; Henry L. Paulson; Sub H. Subramony; Khalaf O. Bushara; Sheng-Han Kuo; Cameron Dietiker; et al. (The Cerebellum, 2024)

Observing Antarctic Bottom Water in the Southern Ocean - Alessandro Silvano; Sarah Purkey; Arnold L. Gordon; Pasquale Castagno; Andrew L. Stewart; Stephen R. Rintoul; Annie Foppert; Kathryn L. Gunn; Laura Herraiz-Borreguero; Shigeru Aoki; Yoshihiro Nakayama; Alberto C. Naveira Garabato; et al. (Frontiers in Marine Science, 2023)
Dense, cold waters formed on Antarctic continental shelves descend along the Antarctic continental margin, where they mix with other Southern Ocean waters to form Antarctic Bottom Water (AABW). AABW then spreads into the deepest parts of all major ocean basins, isolating heat and carbon from the atmosphere for centuries. Despite AABW’s key role in regulating Earth’s climate on long time scales and in recording Southern Ocean conditions, AABW remains poorly observed. This lack of observational data is mostly due to two factors. First, AABW originates on the Antarctic continental shelf and slope where in situ measurements are limited and ocean observations by satellites are hampered by persistent sea ice cover and long periods of darkness in winter. Second, north of the Antarctic continental slope, AABW is found below approximately 2 km depth, where in situ observations are also scarce and satellites cannot provide direct measurements. Here, we review progress made during the past decades in observing AABW. We describe 1) long-term monitoring obtained by moorings, by ship-based surveys, and beneath ice shelves through bore holes; 2) the recent development of autonomous observing tools in coastal Antarctic and deep ocean systems; and 3) alternative approaches including data assimilation models and satellite-derived proxies. The variety of approaches is beginning to transform our understanding of AABW, including its formation processes, temporal variability, and contribution to the lower limb of the global ocean meridional overturning circulation. In particular, these observations highlight the key role played by winds, sea ice, and the Antarctic Ice Sheet in AABW-related processes. We conclude by discussing future avenues for observing and understanding AABW, impressing the need for a sustained and coordinated observing system.

Algal blooms in a river-dominated estuary and nearshore region of Florida, USA: the influence of regulated discharges from water control structures on hydrologic and nutrient conditions - E. J. Phlips; S. Badylak; A. L. Mathews; E. C. Milbrandt; L. R. Montefiore; E. S. Morrison; N. Nelson; B. Stelling (Hydrobiologia, 2023)
Flow-regulated discharges of water from control structures into estuaries result in hydrologic and water chemistry conditions that impact spatial and temporal variability in the structure and biomass of phytoplankton communities, including the potential for harmful algal blooms (HABs). The relationships between regulated Caloosahatchee River (i.e., C-43 Canal) discharges and phytoplankton communities in the Caloosahatchee Estuary and adjacent nearshore regions on the southwest coast of Florida were investigated during two study periods, 2009–2010 and 2018–2019. During periods of low to moderate discharge rates, when mesohaline conditions predominated in the estuary, and water residence times were comparatively long, major blooms of the HAB dinoflagellate species Akashiwo sanguinea were observed in the estuary. Periods of high discharge were characterized by comparatively low phytoplankton biomass in the estuary and greater influence of a wide range of freshwater taxa in the upper reaches. By contrast, intense blooms of the toxic dinoflagellate Karenia brevis in the nearshore region outside of the estuary were observed during high discharge periods in 2018–2019. The latter events were significantly associated with elevated levels of nitrogen in the estuary compared to lower average concentrations in the 2009–2010 study period. The relationships observed in this study provide insights into the importance of managing regulated discharge regimes to minimize adverse impacts of HABs on the health of the estuary and related coastal environments.

Linking knowledge and action for climate-ready fisheries: Emerging best practices across the US - Julia G. Mason; Sarah J. Weisberg; Janelle L. Morano; Richard J. Bell; Mark Fitchett; Roger B. Griffis; Elliott L. Hazen; William D. Heyman; Kirstin Holsman; Kristin M. Kleisner; Katie Westfall; Michele K. Conrad; et al. (Marine Policy, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Beyond ecology: ecosystem restoration as a process for social-ecological transformation - Anazélia M. Tedesco; Sofía López-Cubillos; Robin Chazdon; Jonathan R. Rhodes; Carla L. Archibald; Katharina-Victoria Pérez-Hämmerle; Pedro H.S. Brancalion; Kerrie A. Wilson; Mariana Oliveira; Diego F. Correa; Liz Ota; Tiffany H. Morrison; et al. (Trends in Ecology & Evolution, 2023)

Research priorities for the sustainability of coral-rich western Pacific seascapes - Graeme S. Cumming; Maja Adamska; Michele L. Barnes; Jon Barnett; David R. Bellwood; Joshua E. Cinner; Philippa J. Cohen; Jennifer M. Donelson; Katharina Fabricius; R. Quentin Grafton; Alana Grech; Georgina G. Gurney; et al. (Regional Environmental Change, 2023)
Nearly a billion people depend on tropical seascapes. The need to ensure sustainable use of these vital areas is recognised, as one of 17 policy commitments made by world leaders, in Sustainable Development Goal (SDG) 14 (‘Life below Water’) of the United Nations. SDG 14 seeks to secure marine sustainability by 2030. In a time of increasing social-ecological unpredictability and risk, scientists and policymakers working towards SDG 14 in the Asia–Pacific region need to know: (1) How are seascapes changing? (2) What can global society do about these changes? and (3) How can science and society together achieve sustainable seascape futures? Through a horizon scan, we identified nine emerging research priorities that clarify potential research contributions to marine sustainability in locations with high coral reef abundance. They include research on seascape geological and biological evolution and adaptation; elucidating drivers and mechanisms of change; understanding how seascape functions and services are produced, and how people depend on them; costs, benefits, and trade-offs to people in changing seascapes; improving seascape technologies and practices; learning to govern and manage seascapes for all; sustainable use, justice, and human well-being; bridging communities and epistemologies for innovative, equitable, and scale-crossing solutions; and informing resilient seascape futures through modelling and synthesis. Researchers can contribute to the sustainability of tropical seascapes by co-developing transdisciplinary understandings of people and ecosystems, emphasising the importance of equity and justice, and improving knowledge of key cross-scale and cross-level processes, feedbacks, and thresholds.

Impact of historical legacy pesticides on achieving legislative goals in Europe - J. McGinley; M.G. Healy; P.C. Ryan; J. Harmon O'Driscoll; P.-E. Mellander; L. Morrison; A. Siggins (Science of The Total Environment, 2023)

Spontaneous neoplasia in lions (Panthera leo): combined retrospective case series and literature review - A.F. Rich; I.L. Payne; D. Denk; L. Wilson; L.R. Morrison; M.F. Stidworthy (Journal of Comparative Pathology, 2023)

Coupling large-spatial scale larval dispersal modelling with barcoding to refine the amphi-Atlantic connectivity hypothesis in deep-sea seep mussels - Elodie Portanier; Amandine Nicolle; Willi Rath; Lorraine Monnet; Gregoire Le Goff; Anne-Sophie Le Port; Claire Daguin-Thiébaut; Cheryl L. Morrison; Marina R. Cunha; Melissa Betters; Craig M. Young; Cindy L. Van Dover; et al. (Frontiers in Marine Science, 2023)
In highly fragmented and relatively stable cold-seep ecosystems, species are expected to exhibit high migration rates and long-distance dispersal of long-lived pelagic larvae to maintain genetic integrity over their range. Accordingly, several species inhabiting cold seeps are widely distributed across the whole Atlantic Ocean, with low genetic divergence between metapopulations on both sides of the Atlantic Equatorial Belt (AEB, i.e. Barbados and African/European margins). Two hypotheses may explain such patterns: (i) the occurrence of present-day gene flow or (ii) incomplete lineage sorting due to large population sizes and low mutation rates. Here, we evaluated the first hypothesis using the cold seep mussels Gigantidas childressi, G. mauritanicus, Bathymodiolus heckerae and B. boomerang . We combined COI barcoding of 763 individuals with VIKING20X larval dispersal modelling at a large spatial scale not previously investigated. Population genetics supported the parallel evolution of Gigantidas and Bathymodiolus genera in the Atlantic Ocean and the occurrence of a 1-3 Million-year-old vicariance effect that isolated populations across the Caribbean Sea. Both population genetics and larval dispersal modelling suggested that contemporary gene flow and larval exchanges are possible across the AEB and the Caribbean Sea, although probably rare. When occurring, larval flow was eastward (AEB - only for B. boomerang ) or northward (Caribbean Sea - only for G. mauritanicus ). Caution is nevertheless required since we focused on only one mitochondrial gene, which may underestimate gene flow if a genetic barrier exists. Non-negligible genetic differentiation occurred between Barbados and African populations, so we could not discount the incomplete lineage sorting hypothesis. Larval dispersal modelling simulations supported the genetic findings along the American coast with high amounts of larval flow between the Gulf of Mexico (GoM) and the US Atlantic Margin, although the Blake Ridge population of B. heckerae appeared genetically differentiated. Overall, our results suggest that additional studies using nuclear genetic markers and population genomics approaches are needed to clarify the evolutionary history of the Atlantic bathymodioline mussels and to distinguish between ongoing and past processes.

Active populations and growth of soil microorganisms are framed by mean annual precipitation in three California annual grasslands - Megan M. Foley; Steven J. Blazewicz; Karis J. McFarlane; Alex Greenlon; Michaela Hayer; Jeffrey A. Kimbrel; Benjamin J. Koch; Victoria L. Monsaint-Queeney; Keith Morrison; Ember Morrissey; Bruce A. Hungate; Jennifer Pett-Ridge (Soil Biology and Biochemistry, 2023)

Potential for redistribution of post‐moult habitat for Eudyptes penguins in the Southern Ocean under future climate conditions - Cara‐Paige Green; David B. Green; Norman Ratcliffe; David Thompson; Mary‐Anne Lea; Alastair M. M. Baylis; Alexander L. Bond; Charles‐André Bost; Sarah Crofts; Richard J. Cuthbert; Jacob González‐Solís; Kyle W. Morrison; et al. (Global Change Biology, 2023)
Anthropogenic climate change is resulting in spatial redistributions of many species. We assessed the potential effects of climate change on an abundant and widely distributed group of diving birds, Eudyptes penguins, which are the main avian consumers in the Southern Ocean in terms of biomass consumption. Despite their abundance, several of these species have undergone population declines over the past century, potentially due to changing oceanography and prey availability over the important winter months. We used light‐based geolocation tracking data for 485 individuals deployed between 2006 and 2020 across 10 of the major breeding locations for five taxa of Eudyptes penguins. We used boosted regression tree modelling to quantify post‐moult habitat preference for southern rockhopper ( E. chrysocome ), eastern rockhopper ( E. filholi ), northern rockhopper ( E. moseleyi ) and macaroni/royal ( E. chrysolophus and E. schlegeli ) penguins. We then modelled their redistribution under two climate change scenarios, representative concentration pathways RCP4.5 and RCP8.5 (for the end of the century, 2071–2100). As climate forcings differ regionally, we quantified redistribution in the Atlantic, Central Indian, East Indian, West Pacific and East Pacific regions. We found sea surface temperature and sea surface height to be the most important predictors of current habitat for these penguins; physical features that are changing rapidly in the Southern Ocean. Our results indicated that the less severe RCP4.5 would lead to less habitat loss than the more severe RCP8.5. The five taxa of penguin may experience a general poleward redistribution of their preferred habitat, but with contrasting effects in the (i) change in total area of preferred habitat under climate change (ii) according to geographic region and (iii) the species (macaroni/royal vs. rockhopper populations). Our results provide further understanding on the regional impacts and vulnerability of species to climate change.

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Development of a ddPCR assay for the detection of the Smoky Madtom (Noturus baileyi) from eDNA in stream water samples - Aaron W. Aunins; Michael S. Eackles; Paul E. Super; Matt A. Kulp; Becky J. Nichols; Barbara A. Lubinski; Cheryl L. Morrison; Tim L. King (Conservation Genetics Resources, 2022)
The Smoky Madtom Noturus baileyi is a federally endangered species, whose native distribution includes lower Abrams Creek in Great Smoky Mountains National Park (GRSM) and Citico Creek in nearby Cherokee National Forest. Due to challenges for bio-monitoring posed by its nocturnality and cryptic life history, an environmental DNA (eDNA)-based approach for detection would be useful to complement existing electrofishing and seining efforts to better understand the distribution of this species. We developed a probe-based droplet digital PCR (ddPCR) assay to detect Smoky Madtoms from non-invasively collected water samples. The assay was specific to N. baileyi and did not amplify concentrated genomic DNA of 16 co-occurring or regional fish species, including the yellowfin madtom N. flavipinnis and stonecat N. flavus . The assay limit of detection (LOD) was determined to be 4.18 copies (95% CI: 3.95, 4.41). Several 2 L water samples collected from throughout various streams in GRSM in 2016 and 2017 were tested for the presence of N. baileyi using the ddPCR assay. N. baileyi was detected at two different sites in 2016 and 2017 within Abrams Creek previously known to contain N. baileyi , but no novel detections in other sampled streams were observed. This assay should prove useful for continued surveys of N. baileyi in GRSM.

Detection of Kudoa thyrsites (Myxozoa) eDNA by real‐time and digital PCR from high seawater volumes - Wyth L. Marshall; Tiffany MacWilliam; Kayla Williams; Heather Reinholt; Heidi VanVliet; Danielle New; Meghan Mills; Diane Morrison (Journal of Fish Diseases, 2022)

The S-Factor, a New Measure of Disease Severity in Spinocerebellar Ataxia: Findings and Implications - Louisa P. Selvadurai; Susan L. Perlman; George R. Wilmot; Sub H. Subramony; Christopher M. Gomez; Tetsuo Ashizawa; Henry L. Paulson; Chiadi U. Onyike; Liana S. Rosenthal; Haris I. Sair; Sheng-Han Kuo; Eva-Maria Ratai; et al. (The Cerebellum, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Quantifying the probability of detection of wild ungulates with the Judas technique - David S. L. Ramsey; Karl J. Campbell; Christian Lavoie; Norm Macdonald; Scott A. Morrison (Conservation Biology, 2022)
The Judas technique is often used in control or eradication of particular vertebrate pests. The technique exploits the tendency of individuals to form social groups. A radio collar is affixed to an individual and its subsequent monitoring facilitates the detection of other conspecifics. Efficacy of this technique would be improved if managers could estimate the probability that a Judas individual would detect conspecifics. To calculate this probability, we estimated association rates of Judas individuals with other Judas individuals, given the length of time the Judas has been deployed. We developed a simple model of space‐use for individual Judas animals and constrained detection probabilities to those specific areas. We then combined estimates for individual Judas animals to infer the probability that a wild individual could be detected in an area of interest via Judas surveillance. We illustrated the method by using data from a feral goat eradication program on Isla Santiago, Galápagos, and a feral pig eradication program on Santa Cruz Island, California. Association probabilities declined as the proximity between individual areas of use of a Judas pair decreased. Unconditional probabilities of detection within individual areas of use averaged 0.09 per month for feral pigs and 0.11 per month for feral goats. Probabilities that eradication had been achieved, given no detections of wild conspecifics, and an uninformative prior probability of eradication were 0.79 (90% CI 0.22–0.99) for feral goats and 0.87 (90% CI 0.44–1.0) for feral pigs. We envisage several additions to the analyses used that could improve estimates of Judas detection probability. Analyses such as these can help managers increase the efficacy of eradication efforts, leading to more effective effects to restore native biodiversity.

High resolution C-band SAR backscatter response to peatland water table depth and soil moisture: a laboratory experiment - L. Toca; K. Morrison; R.R.E. Artz; A. Gimona; T. Quaife (International Journal of Remote Sensing, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Responsible agriculture must adapt to the wetland character of mid‐latitude peatlands - Benjamin W. J. Freeman; Chris D. Evans; Samuel Musarika; Ross Morrison; Thomas R. Newman; Susan E. Page; Giles F. S. Wiggs; Nicholle G. A. Bell; David Styles; Yuan Wen; David R. Chadwick; Davey L. Jones (Global Change Biology, 2022)
Drained, lowland agricultural peatlands are greenhouse gas (GHG) emission hotspots and a large but vulnerable store of irrecoverable carbon. They exhibit soil loss rates of ~2.0 cm yr −1 and are estimated to account for 32% of global cropland emissions while producing only 1.1% of crop kilocalories. Carbon dioxide emissions account for >80% of their terrestrial GHG emissions and are largely controlled by water table depth. Reducing drainage depths is, therefore, essential for responsible peatland management. Peatland restoration can substantially reduce emissions. However, this may conflict with societal needs to maintain productive use, to protect food security and livelihoods. Wetland agriculture strategies will, therefore, be required to adapt agriculture to the wetland character of peatlands, and balance GHG mitigation against productivity, where halting emissions is not immediately possible. Paludiculture may substantially reduce GHG emissions but will not always be viable in the current economic landscape. Reduced drainage intensity systems may deliver partial reductions in the rate of emissions, with smaller modifications to existing systems. These compromise systems may face fewer hurdles to adoption and minimize environmental harm until societal conditions favour strategies that can halt emissions. Wetland agriculture will face agronomic, socio‐economic and water management challenges, and careful implementation will be required. Diversity of values and priorities among stakeholders creates the potential for conflict. Successful implementation will require participatory research approaches and co‐creation of workable solutions. Policymakers, private sector funders and researchers have key roles to play but adoption risks would fall predominantly on land managers. Development of a robust wetland agriculture paradigm is essential to deliver resilient production systems and wider environmental benefits. The challenge of responsible use presents an opportunity to rethink peatland management and create thriving, innovative and green wetland landscapes for everyone's future benefit, while making a vital contribution to global climate change mitigation.

Conventional versus drug-eluting embolic transarterial chemoembolization with doxorubicin: comparative drug delivery, pharmacokinetics, and treatment response in a rabbit VX2 tumor model - Ron C. Gaba; Ramzy C. Khabbaz; Ruth N. Muchiri; Joseph D. Morrison; Lobna Elkhadragy; William M. Totura; Jonathan P. Samuelson; Herbert E. Whiteley; Ryan L. Deaton; Peter L. Nguyen; Maria Sverdlov; Jeremy J. Johnson; et al. (Drug Delivery and Translational Research, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Ethics and governance for internet‐based conservation science research - Ruth M. Thompson; Jordan Hall; Chris Morrison; Nicole R. Palmer; David L. Roberts (Conservation Biology, 2021)
Internet‐based research is increasingly important for conservation science and has wide‐ranging applications and contexts, including culturomics, illegal wildlife trade, and citizen science. However, online research methods pose a range of ethical and legal challenges. Online data may be protected by copyright, database rights, or contract law. Privacy rights may also restrict the use and access of data, as well as ethical requirements from institutions. Online data have real‐world meaning, and the ethical treatment of individuals and communities must not be marginalized when conducting internet‐based research. As ethics frameworks originally developed for biomedical applications are inadequate for these methods, we propose that research activities involving the analysis of preexisting online data be treated analogous to offline social science methods, in particular, nondeceptive covert observation. By treating internet users and their data with respect and due consideration, conservationists can uphold the public trust needed to effectively address real‐world issues.

Drought at a coastal wetland affects refuelling and migration strategies of shorebirds - Alexandra M. Anderson; Christian Friis; Cheri L. Gratto-Trevor; Christopher M. Harris; Oliver P. Love; R. I. Guy Morrison; Sean W. J. Prosser; Erica Nol; Paul A. Smith (Oecologia, 2021)
Droughts can affect invertebrate communities in wetlands, which can have bottom-up effects on the condition and survival of top predators. Shorebirds, key predators at coastal wetlands, have experienced widespread population declines and could be negatively affected by droughts. We explored, in detail, the effects of drought on multiple aspects of shorebird stopover and migration ecology by contrasting a year with average wet/dry conditions (2016) with a year with moderate drought (2017) at a major subarctic stopover site on southbound migration. We also examined the effects of drought on shorebird body mass during stopover across 14 years (historical: 1974–1982 and present-day: 2014–2018). For the detailed comparison of two years, in the year with moderate drought we documented lower invertebrate abundance at some sites, higher prey family richness in shorebird faecal samples, lower shorebird refuelling rates, shorter stopover durations for juveniles, and, for most species, a higher probability of making a subsequent stopover in North America after departing the subarctic, compared to the year with average wet/dry conditions. In the 14-year dataset, shorebird body mass tended to be lower in drier years. We show that even short-term, moderate drought conditions can negatively affect shorebird refuelling performance at coastal wetlands, which may carry-over to affect subsequent stopover decisions. Given shorebird population declines and predicted changes in the severity and duration of droughts with climate change, researchers should prioritize a better understanding of how droughts affect shorebird refuelling performance and survival.

Variation in herpetofauna detection probabilities: implications for study design - Jeremy A. Baumgardt; Michael L. Morrison; Leonard A. Brennan; Madeleine Thornley; Tyler A. Campbell (Environmental Monitoring and Assessment, 2021)
Population monitoring is fundamental for informing management decisions aimed at reducing the rapid rate of global biodiversity decline. Herpetofauna are experiencing declines worldwide and include species that are challenging to monitor. Raw counts and associated metrics such as richness indices are common for monitoring populations of herpetofauna; however, these methods are susceptible to bias as they fail to account for varying detection probabilities. Our goal was to develop a program for efficiently monitoring herpetofauna in southern Texas. Our objectives were to (1) estimate detection probabilities in an occupancy modeling framework using trap arrays for a diverse group of herpetofauna and (2) to evaluate the relative effectiveness of funnel traps, pitfall traps, and cover boards. We collected data with 36 arrays at 2 study sites in 2015 and 2016, for 2105 array-days resulting in 4839 detections of 51 species. We modeled occupancy for 21 species and found support for the hypothesis that detection probability varied over our sampling duration for 10 species and with rainfall for 10 species. For herpetofauna in our study, we found 14 and 12 species were most efficiently captured with funnel traps and pitfall traps, respectively, and no species were most efficiently captured with cover boards. Our results show that using methods that do not account for variations in detection probability are highly subject to bias unless the likelihood of false absences is minimized with exceptionally long capture durations. For monitoring herpetofauna in southern Texas, we recommend using arrays with funnel and pitfall traps and an analytical method such as occupancy modeling that accounts for variation in detection.

Climate Change Implications for Tidal Marshes and Food Web Linkages to Estuarine and Coastal Nekton - Denise D. Colombano; Steven Y. Litvin; Shelby L. Ziegler; Scott B. Alford; Ronald Baker; Myriam A. Barbeau; Just Cebrián; Rod M. Connolly; Carolyn A. Currin; Linda A. Deegan; Justin S. Lesser; Charles W. Martin; et al. (Estuaries and Coasts, 2021)
Climate change is altering naturally fluctuating environmental conditions in coastal and estuarine ecosystems across the globe. Departures from long-term averages and ranges of environmental variables are increasingly being observed as directional changes [e.g., rising sea levels, sea surface temperatures (SST)] and less predictable periodic cycles (e.g., Atlantic or Pacific decadal oscillations) and extremes (e.g., coastal flooding, marine heatwaves). Quantifying the short- and long-term impacts of climate change on tidal marsh seascape structure and function for nekton is a critical step toward fisheries conservation and management. The multiple stressor framework provides a promising approach for advancing integrative, cross-disciplinary research on tidal marshes and food web dynamics. It can be used to quantify climate change effects on and interactions between coastal oceans (e.g., SST, ocean currents, waves) and watersheds (e.g., precipitation, river flows), tidal marsh geomorphology (e.g., vegetation structure, elevation capital, sedimentation), and estuarine and coastal nekton (e.g., species distributions, life history adaptations, predator-prey dynamics). However, disentangling the cumulative impacts of multiple interacting stressors on tidal marshes, whether the effects are additive, synergistic, or antagonistic, and the time scales at which they occur, poses a significant research challenge. This perspective highlights the key physical and ecological processes affecting tidal marshes, with an emphasis on the trophic linkages between marsh production and estuarine and coastal nekton, recommended for consideration in future climate change studies. Such studies are urgently needed to understand climate change effects on tidal marshes now and into the future.

Human Actions Alter Tidal Marsh Seascapes and the Provision of Ecosystem Services - Ben L. Gilby; Michael P. Weinstein; Ronald Baker; Just Cebrian; Scott B. Alford; Ariella Chelsky; Denise Colombano; Rod M. Connolly; Carolyn A. Currin; Ilka C. Feller; Alyssa Frank; Janelle A. Goeke; et al. (Estuaries and Coasts, 2021)

Differential and interacting impacts of invasive plants and white-tailed deer in eastern U.S. forests - David L. Gorchov; Bernd Blossey; Kristine M. Averill; Andrea Dávalos; J. Mason Heberling; Michael A. Jenkins; Susan Kalisz; William J. McShea; Janet A. Morrison; Victoria Nuzzo; Christopher R. Webster; Donald M. Waller (Biological Invasions, 2021)

Impacts of zebra mussels (Dreissena polymorpha) on isotopic niche size and niche overlap among fish species in a mesotrophic lake - Alexandra L. Morrison; Mary A. Thelen; Sarah E. Howe; Kyle D. Zimmer; Brian R. Herwig; David F. Staples; Margaret C. McEachran (Biological Invasions, 2021)

Freshwater early life growth influences partial migration in populations of Dolly Varden (Salvelinus malma malma) - Christie M. Morrison; Colin P. Gallagher; Keith B. Tierney; Kimberly L. Howland (Polar Biology, 2021)
Populations of northern Dolly Varden ( Salvelinus malma malma ) exhibit partial seaward migration, yet little is known about this phenomenon in Dolly Varden populations. Our study analyzed data from three different Dolly Varden populations in the western Canadian Arctic in order to determine if: (1) differences in size-at-first seaward migration exist between fish that migrate at early and late ages among populations inhabiting different river systems, and (2) annual growth influences anadromous or resident life history choice. Otolith strontium analysis and back-calculation were used to determine age- and size-at-first seaward migration, respectively. Differences in age- and size-at-first seaward migration were determined across river system and migration age. Back-calculated fish lengths were compared using a mixed effect model to determine how early growth influences migratory tactics (early or late aged smolt, or resident). Our results indicate that fish exhibiting faster early growth migrated in earlier years and at smaller sizes than slower growing fish, however size- and age-at first seaward migration varied by river system. Faster growing Dolly Varden tended to become either residents or early smolts, while slower growth was associated with smolting later in life. This is contrary to life history theory where the fastest growing fish in a population should mature as a resident. Our results indicate factors other than growth may be influencing life history ‘decisions’ in Dolly Varden. Future work on growth efficiencies and metabolic rates is needed to assess how they affect migratory behaviours.

Temporary threshold shift after noise exposure in hypobaric hypoxia at high altitude: results of the ADEMED expedition 2011 - K. Fehrenbacher; C. Apel; D. Bertsch; M. S. van der Giet; S. van der Giet; M. Grass; C. Gschwandtl; N. Heussen; N. Hundt; C. Kühn; A. Morrison; M. Müller-Ost; et al. (International Archives of Occupational and Environmental Health, 2021)
Objectives To evaluate whether there is an increased risk for noise-induced hearing loss at high altitude rsp. in hypobaric hypoxia. Methods Thirteen volunteers got standard audiometry at 125, 250, 500, 750, 1000, 1500, 2000, 3000, 4000, 6000, and 8000 Hz before and after 10 min of white noise at 90 dB. The system was calibrated for the respective altitude. Measurements were performed at Kathmandu (1400 m) and at Gorak Shep (5300 m) (Solo Khumbu/Nepal) after 10 days of acclimatization while on trek. Temporary threshold shift (TTS) was analyzed by descriptive statistics and by factor analysis. Results TTS is significantly more pronounced at high altitudes. Acclimatization does not provide any protection of the inner ear, although it increases arterial oxygen saturation. Conclusion The thresholds beyond which noise protection is recommended (> 80 dB) or necessary (> 85 dB) are not sufficient at high altitudes. We suggest providing protective devices above an altitude of 1500 m (“ear threshold altitude”) when noise level is higher than 75 dB and using them definitively above 80 dB. This takes the individual reaction on hypobaric hypoxia at high altitude into account.

Factors Associated with Listing Decisions under the U.S. Endangered Species Act - Kathryn N. Smith-Hicks; Michael L. Morrison (Environmental Management, 2021)

Effects of temperature on sexual development in steelhead, Oncorhynchus mykiss - Kathleen S. Cole; David L. G. Noakes; Neil Thompson; Michael Blouin; Bruce Morrison; Ryan B. Couture; Joseph O’Neil; Carl B. Schreck (Environmental Biology of Fishes, 2021)

Source Switching Maintains Dissolved Organic Matter Chemostasis Across Discharge Levels in a Large Temperate River Network - J. D. Hosen; K. S. Aho; J. H. Fair; E. D. Kyzivat; S. Matt; J. Morrison; A. Stubbins; L. C. Weber; B. Yoon; P. A. Raymond (Ecosystems, 2021)

Antisense Oligonucleotide Therapy Targeted Against ATXN3 Improves Potassium Channel–Mediated Purkinje Neuron Dysfunction in Spinocerebellar Ataxia Type 3 - David D. Bushart; Annie J. Zalon; Hongjiu Zhang; Logan M. Morrison; Yuanfang Guan; Henry L. Paulson; Vikram G. Shakkottai; Hayley S. McLoughlin (The Cerebellum, 2021)

A Phase I Study to Evaluate Two Doses of Wharton’s Jelly-Derived Mesenchymal Stromal Cells for the Treatment of De Novo High-Risk or Steroid-Refractory Acute Graft Versus Host Disease - Rupal P. Soder; Buddhadeb Dawn; Mark L. Weiss; Neil Dunavin; Scott Weir; James Mitchell; Meizhang Li; Leyla Shune; Anurag K. Singh; Siddhartha Ganguly; Marc Morrison; Haitham Abdelhakim; et al. (Stem Cell Reviews and Reports, 2020)

Distinct responses of antagonistic and mutualistic networks to agricultural intensification - Beth M. L. Morrison; Rodolfo Dirzo (Ecology, 2020)
Species interaction networks, which govern the maintenance of biodiversity and ecosystem processes within ecological communities, are being rapidly altered by anthropogenic activities worldwide. Studies on the response of species interaction networks to anthropogenic disturbance have almost exclusively focused on one interaction type at a time, such as mutualistic or antagonistic interactions, making it challenging to decipher how networks of different interaction types respond to the same anthropogenic disturbance. Moreover, few studies have simultaneously focused on the two main components of network structure: network topology (i.e., architecture) and network ecology (i.e., species identities and interaction turnover), thereby limiting our understanding of the ecological drivers underlying changes in network topology in response to anthropogenic disturbance. Here, we used 16,400 plant–pollinator and plant–herbivore interaction observations from 16 sites along an agricultural intensification gradient to compare changes in network topology and ecology between mutualistic and antagonistic networks. We measured two aspects of network topology—nestedness and modularity—and found that although the mutualistic networks were consistently more nested than antagonistic networks and antagonistic networks were consistently more modular, the rate of change in nestedness and modularity along the gradient was comparable between the two network types. Change in network ecology, however, was distinct between mutualistic and antagonistic networks, with partner switching making a significantly larger contribution to interaction turnover in the mutualistic networks than in the antagonistic networks, and species turnover being a strong contributor to interaction turnover in the antagonistic networks. The ecological and topological changes we observed in the antagonistic and mutualistic networks have different implications for pollinator and herbivore communities in agricultural landscapes, and support the idea that pollinators are more labile in their interaction partner choice, whereas herbivores form more reciprocally specialized, and therefore more vulnerable, interactions. Our results also demonstrate that studying both topological and ecological network structure can help to elucidate the effects of anthropogenic disturbance on ecological communities, with applications for conservation and restoration of species interactions and the ecosystem processes they maintain.

Prescription analgesia and adjuvant use by pain severity at admission among nursing home residents with non-malignant pain - Kate L. Lapane; Anne L. Hume; Reynolds A. Morrison; Bill M. Jesdale (European Journal of Clinical Pharmacology, 2020)
Objective We estimated the use of prescribed analgesics and adjuvants among nursing home residents without cancer who reported pain at their admission assessment, in relation to resident-reported pain severity. Methods Medicare Part D claims were used to define 3 classes of analgesics and 7 classes of potential adjuvants on the 21st day after nursing home admission (or the day of discharge for residents discharged before that date) among 180,780 residents with complete information admitted between January 1, 2011 and December 9, 2016, with no cancer diagnosis. Results Of these residents, 27.9% reported mild pain, 46.6% moderate pain, and 25.6% reported severe pain. The prevalence of residents in pain without Part D claims for prescribed analgesic and/or adjuvant medications was 47.3% among those reporting mild pain, 35.7% among those with moderate pain, and 24.8% among those in severe pain. Among residents reporting severe pain, 33% of those ≥ 85 years of age and 35% of those moderately cognitively impaired received no prescription analgesics/adjuvants. Use of all classes of prescribed analgesics and adjuvants increased with resident-reported pain severity, and the concomitant use of medications from multiple classes was common. Conclusion Among nursing home residents with recognized pain, opportunities to improve the pharmacologic management of pain, especially among older residents, and those living with cognitive impairments exist.

Effect of Simvastatin on Permeability in Cerebral Cavernous Malformation Type 1 Patients: Results from a Pilot Small Randomized Controlled Clinical Trial - Marc C Mabray; Arvind Caprihan; Jeffrey Nelson; Charles E. McCulloch; Atif Zafar; Helen Kim; Blaine L Hart; Leslie Morrison (Translational Stroke Research, 2020)

Immune differences in captive and free-ranging zebras (Equus zebra and E. quagga) - Peter A. Seeber; Thomas Morrison; Alix Ortega; Marion L. East; Alex D. Greenwood; Gábor Á. Czirják (Mammalian Biology, 2020)
Wild mammals in ex situ captivity experience substantially different environmental conditions compared to free-ranging conspecifics, e.g., in terms of diet, climatic conditions, social factors, movement space, and direct anthropogenic disturbance. Moreover, animals in captivity frequently undergo management interventions such as medical treatments which may influence pathogen pressure. Captivity is known to affect immunological responses in some terrestrial and marine mammals; however, it is unclear whether this can be generalized to other taxa. Furthermore, little is known about how energetically costly life history stages such as lactation influence the immune system in wildlife. We measured expression of components of the constitutive and induced innate immunity and of the adaptive immune system in plains and mountain zebras ( Equus quagga and E. zebra ), including lactating and non-lactating individuals. As a proxy for general immune function, we screened for lytic equine herpesvirus (EHV) infection, a common and often latent pathogen which is reactivated in response to stress and immune challenge. Both energetically cheap markers of the constitutive innate immunity were lower in captive than in wild zebras, whereas energetically costly markers of the induced innate immunity were more highly expressed in captive zebras. Lactation was associated with higher titers of natural antibodies and lysozyme. Lytic EHV infection was not significantly correlated with any of the measured immune markers. Our results suggest that captivity and lactation may influence immune functions in zebra mares.

Quantifying student engagement in learning about climate change using galvanic hand sensors in a controlled educational setting - A. L. Morrison; S. Rozak; A. U. Gold; J. E. Kay (Climatic Change, 2020)

Agricultural intensification drives changes in hybrid network robustness by modifying network structure - Beth M. L. Morrison; Berry J. Brosi; Rodolfo Dirzo (Ecology Letters, 2020)
Within ecological communities, species engage in myriad interaction types, yet empirical examples of hybrid species interaction networks composed of multiple types of interactions are still scarce. A key knowledge gap is understanding how the structure and stability of such hybrid networks are affected by anthropogenic disturbance. Using 15,169 interaction observations, we constructed 16 hybrid herbivore‐plant‐pollinator networks along an agricultural intensification gradient to explore changes in network structure and robustness to local extinctions. We found that agricultural intensification led to declines in modularity but increases in nestedness and connectance. Notably, network connectance, a structural feature typically thought to increase robustness, caused declines in hybrid network robustness, but the directionality of changes in robustness along the gradient depended on the order of local species extinctions. Our results not only demonstrate the impacts of anthropogenic disturbance on hybrid network structure, but they also provide unexpected insights into the structure‐stability relationship of hybrid networks.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Phenotypic Plasticity or a Reproductive Dead End? Primnoa pacifica (Cnidaria: Alcyonacea) in the Southeastern Alaska Region - Rhian G. Waller; Robert P. Stone; Lauren N. Rice; Julia Johnstone; Ashley M. Rossin; Elise Hartill; Keri Feehan; Cheryl L. Morrison (Frontiers in Marine Science, 2019)

Anthropogenic modifications to fire regimes in the wider Serengeti‐Mara ecosystem - James R. Probert; Catherine L. Parr; Ricardo M. Holdo; T. Michael Anderson; Sally Archibald; Colin J. Courtney Mustaphi; Andrew P. Dobson; Jason E. Donaldson; Grant C. Hopcraft; Gareth P. Hempson; Thomas A. Morrison; Colin M. Beale (Global Change Biology, 2019)
Fire is a key driver in savannah systems and widely used as a land management tool. Intensifying human land uses are leading to rapid changes in the fire regimes, with consequences for ecosystem functioning and composition. We undertake a novel analysis describing spatial patterns in the fire regime of the Serengeti‐Mara ecosystem, document multidecadal temporal changes and investigate the factors underlying these patterns. We used MODIS active fire and burned area products from 2001 to 2014 to identify individual fires; summarizing four characteristics for each detected fire: size, ignition date, time since last fire and radiative power. Using satellite imagery, we estimated the rate of change in the density of livestock bomas as a proxy for livestock density. We used these metrics to model drivers of variation in the four fire characteristics, as well as total number of fires and total area burned. Fires in the Serengeti‐Mara show high spatial variability—with number of fires and ignition date mirroring mean annual precipitation. The short‐term effect of rainfall decreases fire size and intensity but cumulative rainfall over several years leads to increased standing grass biomass and fuel loads, and, therefore, in larger and hotter fires. Our study reveals dramatic changes over time, with a reduction in total number of fires and total area burned, to the point where some areas now experience virtually no fire. We suggest that increasing livestock numbers are driving this decline, presumably by inhibiting fire spread. These temporal patterns are part of a global decline in total area burned, especially in savannahs, and we caution that ecosystem functioning may have been compromised. Land managers and policy formulators need to factor in rapid fire regime modifications to achieve management objectives and maintain the ecological function of savannah ecosystems.

Growth and reproductive characteristics of rarely observed resident female Dolly Varden (Salvelinus malma malma) in North America - Colin P. Gallagher; Christie M. Morrison; Ellen V. Lea; Norman M. Halden; Kimberly L. Howland (Hydrobiologia, 2019)

Building the Knowledge-to-Action Pipeline in North America: Connecting Ocean Acidification Research and Actionable Decision Support - Jessica N. Cross; Jessie A. Turner; Sarah R. Cooley; Jan A. Newton; Kumiko Azetsu-Scott; R. Christopher Chambers; Darcy Dugan; Kaitlin Goldsmith; Helen Gurney-Smith; Alexandra R. Harper; Elizabeth B. Jewett; Denise Joy; et al. (Frontiers in Marine Science, 2019)

Merlin modulates process outgrowth and synaptogenesis in the cerebellum - A. Toledo; F. Lang; M. Doengi; H. Morrison; V. Stein; S. L. Baader (Brain Structure and Function, 2019)

Enhancement of primary production during drought in a temperate watershed is greater in larger rivers than headwater streams - J. D. Hosen; K. S. Aho; A. P. Appling; E. C. Creech; J. H. Fair; R. O. Hall; E. D. Kyzivat; R. S. Lowenthal; S. Matt; J. Morrison; J. E. Saiers; J. B. Shanley; et al. (Limnology and Oceanography, 2019)
Drought is common in rivers, yet how this disturbance regulates metabolic activity across network scales is largely unknown. Drought often lowers gross primary production (GPP) and ecosystem respiration (ER) in small headwaters but by contrast can enhance GPP and cause algal blooms in downstream estuaries. We estimated ecosystem metabolism across a nested network of 13 reaches from headwaters to the main stem of the Connecticut River from 2015 through 2017, which encompassed a pronounced drought. During drought, GPP and ER increased, but with greater enhancement in larger rivers. Responses of GPP and ER were partially due to warmer temperatures associated with drought, particularly in the larger rivers where temperatures during summer drought were > 10°C higher than typical summer baseflow. The larger rivers also had low canopy cover, which allowed primary producers to take advantage of lower turbidity and fewer cloudy days during drought. We conclude that GPP is enhanced by higher temperature, lower turbidity, and longer water residence times that are all a function of low discharge, but ecosystem response in temperate watersheds to these drivers depends on light availability regulated by riparian canopy cover. In larger rivers, GPP increased more than ER during drought, even leading to temporary autotrophy, an otherwise rare event in the typically light‐limited heterotrophic Connecticut River main stem. With climate change, rivers and streams may become warmer and drought frequency and severity may increase. Such changes may increase autotrophy in rivers with broad implications for carbon cycling and water quality in aquatic ecosystems.

Leveraging linkage evidence to identify low-frequency and rare variants on 16p13 associated with blood pressure using TOPMed whole genome sequencing data - Karen Y. He; Xiaoyin Li; Tanika N. Kelly; Jingjing Liang; Brian E. Cade; Themistocles L. Assimes; Lewis C. Becker; Amber L. Beitelshees; Adam P. Bress; Yen-Pei Christy Chang; Yii-Der Ida Chen; Paul S. de Vries; et al. (Human Genetics, 2019)

Differential Proteomics for Distinguishing Ischemic Stroke from Controls: a Pilot Study of the SpecTRA Project - A. M. Penn; V. Saly; A. Trivedi; M. L. Lesperance; K. Votova; A. M. Jackson; N.S. Croteau; R. F. Balshaw; M. B. Bibok; D. S. Smith; K. K. Lam; J. Morrison; et al. (Translational Stroke Research, 2018)

Characterization of isolated liver sinusoidal endothelial cells for liver bioengineering - A. M. Dingle; K. K. Yap; Y-W. Gerrand; C. J. Taylor; E. Keramidaris; Z. Lokmic; A. M. Kong; H. L. Peters; W. A. Morrison; G. M. Mitchell (Angiogenesis, 2018)

Corrigendum: Frequency of Microplastics in Mesopelagic Fishes from the Northwest Atlantic - Alina M. Wieczorek; Liam Morrison; Peter L. Croot; A. Louise Allcock; Eoin MacLoughlin; Olivier Savard; Hannah Brownlow; Thomas K. Doyle (Frontiers in Marine Science, 2018)

Effect of intranasal esketamine on cognitive functioning in healthy participants: a randomized, double-blind, placebo-controlled study - Randall L. Morrison; Maggie Fedgchin; Jaskaran Singh; Joop Van Gerven; Rob Zuiker; Kyoung Soo Lim; Peter van der Ark; Ewa Wajs; Liwen Xi; Peter Zannikos; Wayne C. Drevets (Psychopharmacology, 2018)

Correction to: Genetic and morphological sex identification methods reveal a male-biased sex ratio in the Ivory Gull Pagophila eburnea - Glenn Yannic; Thomas Broquet; Hallvard Strøm; Adrian Aebischer; Christophe Dufresnes; Maria V. Gavrilo; H. Grant Gilchrist; Mark L. Mallory; R. I. Guy Morrison; Brigitte Sabard; Roberto Sermier; Olivier Gilg (Journal of Ornithology, 2018)

Pyrodiversity interacts with rainfall to increase bird and mammal richness in African savannas - Colin M. Beale; Colin J. Courtney Mustaphi; Thomas A. Morrison; Sally Archibald; T. Michael Anderson; Andrew P. Dobson; Jason E. Donaldson; Gareth P. Hempson; James Probert; Catherine L. Parr (Ecology Letters, 2018)
Fire is a fundamental process in savannas and is widely used for management. Pyrodiversity, variation in local fire characteristics, has been proposed as a driver of biodiversity although empirical evidence is equivocal. Using a new measure of pyrodiversity (Hempson et al .), we undertook the first continent‐wide assessment of how pyrodiversity affects biodiversity in protected areas across African savannas. The influence of pyrodiversity on bird and mammal species richness varied with rainfall: strongest support for a positive effect occurred in wet savannas (> 650 mm/year), where species richness increased by 27% for mammals and 40% for birds in the most pyrodiverse regions. Range‐restricted birds were most increased by pyrodiversity, suggesting the diversity of fire regimes increases the availability of rare niches. Our findings are significant because they explain the conflicting results found in previous studies of savannas. We argue that managing savanna landscapes to increase pyrodiversity is especially important in wet savannas.

Transcriptome profiles of sunflower reveal the potential role of microsatellites in gene expression divergence - Chathurani Ranathunge; Gregory L. Wheeler; Melody E. Chimahusky; Meaghan M. Kennedy; Jesse I. Morrison; Brian S. Baldwin; Andy D. Perkins; Mark E. Welch (Molecular Ecology, 2018)
The mechanisms by which natural populations generate adaptive genetic variation are not well understood. Some studies propose that microsatellites can function as drivers of adaptive variation. Here, we tested a potentially adaptive role for transcribed microsatellites with natural populations of the common sunflower ( Helianthus annuus L.) by assessing the enrichment of microsatellites in genes that show expression divergence across latitudes. Seeds collected from six populations at two distinct latitudes in Kansas and Oklahoma were planted and grown in a common garden. Morphological measurements from the common garden demonstrated that phenotypic variation among populations is largely explained by underlying genetic variation. An RNA‐Seq experiment was conducted with 96 of the individuals grown in the common garden and differentially expressed (DE) transcripts between the two latitudes were identified. A total number of 825 DE transcripts were identified. DE transcripts and nondifferentially expressed (NDE) transcripts were then scanned for microsatellites. The abundance of different motif lengths and types in both groups were estimated. Our results indicate that DE transcripts are significantly enriched with mononucleotide repeats and significantly depauperate in trinucleotide repeats. Further, the standardized mononucleotide repeat motif A and dinucleotide repeat motif AG were significantly enriched within DE transcripts while motif types, C, AT, ACC and AAC in DE transcripts, are significantly differentiated in microsatellite tract length between the two latitudes. The tract length differentiation at specific microsatellite motif types across latitudes and their enrichment within DE transcripts indicate a potential functional role for transcribed microsatellites in gene expression divergence in sunflower.

Frequency of Microplastics in Mesopelagic Fishes from the Northwest Atlantic - Alina M. Wieczorek; Liam Morrison; Peter L. Croot; A. Louise Allcock; Eoin MacLoughlin; Olivier Savard; Hannah Brownlow; Thomas K. Doyle (Frontiers in Marine Science, 2018)

Genetic variants in microRNA genes and targets associated with cardiovascular disease risk factors in the African-American population - Chang Li; Megan L. Grove; Bing Yu; Barbara C. Jones; Alanna Morrison; Eric Boerwinkle; Xiaoming Liu (Human Genetics, 2018)

Indigenous arthropod natural enemies of the invasive brown marmorated stink bug in North America and Europe - Paul K. Abram; Kim A. Hoelmer; Angelita Acebes-Doria; Heather Andrews; Elizabeth H. Beers; J. Christopher Bergh; Ric Bessin; David Biddinger; Paul Botch; Matthew L. Buffington; Mary L. Cornelius; Elena Costi; et al. (Journal of Pest Science, 2017)

Chemical ecology of Halyomorpha halys: discoveries and applications - Donald C. Weber; William R. Morrison; Ashot Khrimian; Kevin B. Rice; Tracy C. Leskey; Cesar Rodriguez-Saona; Anne L. Nielsen; Brett R. Blaauw (Journal of Pest Science, 2017)

Medical Knowledge Assessment by Hematology and Medical Oncology In-Training Examinations Are Better Than Program Director Assessments at Predicting Subspecialty Certification Examination Performance - Frances A. Collichio; Brian J. Hess; Elaine A. Muchmore; Lauren Duhigg; Rebecca S. Lipner; Steven Haist; Janine L. Hawley; Carol A. Morrison; Charles P. Clayton; Marilyn J. Raymond; Karen M. Kayoumi; Scott D. Gitlin (Journal of Cancer Education, 2017)

Responses of a Federally Endangered Songbird to Understory Thinning in Oak-Juniper Woodlands - Ashley M. Long; Mike E. Marshall; Michael L. Morrison; K. Brian Hays; Shannon L. Farrell (Environmental Management, 2017)

Mycorrhizal inoculation increases genes associated with nitrification and improved nutrient retention in soil - E. Morrison; L. Lagos; A. Al-Agely; H. Glaab; Winston Johnson; Milko A. Jorquera; A. Ogram (Biology and Fertility of Soils, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Recent Advances in Arctic Cloud and Climate Research - Jennifer E. Kay; Tristan L’Ecuyer; Helene Chepfer; Norman Loeb; Ariel Morrison; Gregory Cesana (Current Climate Change Reports, 2016)

Spatial distribution and the value of green spaces for urban red-tailed hawks - Joan L. Morrison; Isabel G. W. Gottlieb; Kyle E. Pias (Urban Ecosystems, 2016)

Uncovering pathways of metal contamination with microscopic techniques and lead isotopic tracing - J. J. Davis; A. L. Morrison; B. L. Gulson (Australian Journal of Earth Sciences, 2016)

Long‐term epidemiological survey of Kudoa thyrsites (Myxozoa) in Atlantic salmon ( Salmo salar L.) from commercial aquaculture farms - W L Marshall; A Sitjà‐Bobadilla; H M Brown; T MacWilliam; Z Richmond; H Lamson; D B Morrison; L O B Afonso (Journal of Fish Diseases, 2016)
Kudoa thyrsites (Myxozoa) encysts within myocytes of a variety of fishes. While infected fish appear unharmed, parasite‐derived enzymes degrade the flesh post‐mortem. In regions of British Columbia ( BC ), Canada, up to 4–7% of fillets can be affected, thus having economic consequences and impacting the competitiveness of BC 's farms. K. thyrsites was monitored in two farms having high ( HP ) or low ( LP ) historical infection prevalence. At each farm, 30 fish were sampled monthly for blood and muscle during the first year followed by nine samplings during year two. Prevalence and intensity were measured by PCR and histology of muscle samples. In parallel, fillet tests were used to quantify myoliquefaction. Infections were detected by PCR after 355 and 509 degree days at LP and HP farms, respectively. Prevalence reached 100% at the HP farm by 2265 degree days and declined during the second year, whereas it plateaued near 50% at the LP farm. Infection intensities decreased after 1 year at both farms. Blood was PCR ‐positive at both farms between 778 and 1113 degree days and again after 2000 degree days. This is the first monitoring project in a production environment and compares data between farms with different prevalence.

Genetic and morphological sex identification methods reveal a male-biased sex ratio in the Ivory Gull Pagophila eburnea - Glenn Yannic; Thomas Broquet; Hallvard Strøm; Adrian Aebischer; Christophe Dufresnes; Maria V. Gavrilo; H. Grant Gilchrist; Mark L. Mallory; R. I. Guy Morrison; Brigitte Sabard; Roberto Sermier; Olivier Gilg (Journal of Ornithology, 2016)

Adaptive divergence despite strong genetic drift: genomic analysis of the evolutionary mechanisms causing genetic differentiation in the island fox ( Urocyon littoralis ) - W. Chris Funk; Robert E. Lovich; Paul A. Hohenlohe; Courtney A. Hofman; Scott A. Morrison; T. Scott Sillett; Cameron K. Ghalambor; Jesus E. Maldonado; Torben C. Rick; Mitch D. Day; Nicholas R. Polato; Sarah W. Fitzpatrick; et al. (Molecular Ecology, 2016)
The evolutionary mechanisms generating the tremendous biodiversity of islands have long fascinated evolutionary biologists. Genetic drift and divergent selection are predicted to be strong on islands and both could drive population divergence and speciation. Alternatively, strong genetic drift may preclude adaptation. We conducted a genomic analysis to test the roles of genetic drift and divergent selection in causing genetic differentiation among populations of the island fox ( Urocyon littoralis ). This species consists of six subspecies, each of which occupies a different California Channel Island. Analysis of 5293 SNP loci generated using Restriction‐site Associated DNA ( RAD ) sequencing found support for genetic drift as the dominant evolutionary mechanism driving population divergence among island fox populations. In particular, populations had exceptionally low genetic variation, small N e (range = 2.1–89.7; median = 19.4), and significant genetic signatures of bottlenecks. Moreover, islands with the lowest genetic variation (and, by inference, the strongest historical genetic drift) were most genetically differentiated from mainland grey foxes, and vice versa, indicating genetic drift drives genome‐wide divergence. Nonetheless, outlier tests identified 3.6–6.6% of loci as high F ST outliers, suggesting that despite strong genetic drift, divergent selection contributes to population divergence. Patterns of similarity among populations based on high F ST outliers mirrored patterns based on morphology, providing additional evidence that outliers reflect adaptive divergence. Extremely low genetic variation and small N e in some island fox populations, particularly on San Nicolas Island, suggest that they may be vulnerable to fixation of deleterious alleles, decreased fitness and reduced adaptive potential.

Greater soil C inputs accelerate loss of C in cropping systems with low N input - A. Diochon; E. G. Gregorich; L. Kellman; M. Morrison; B.-L. Ma (Plant and Soil, 2016)

High connectivity in a long-lived high-Arctic seabird, the ivory gull Pagophila eburnea - Glenn Yannic; Jonathan M. Yearsley; Roberto Sermier; Christophe Dufresnes; Olivier Gilg; Adrian Aebischer; Maria V. Gavrilo; Hallvard Strøm; Mark L. Mallory; R. I. Guy Morrison; H. Grant Gilchrist; Thomas Broquet (Polar Biology, 2016)

Microbial biofilms associated with intravascular catheter-related bloodstream infections in adult intensive care patients - L. Zhang; J. Gowardman; M. Morrison; N. Runnegar; C. M. Rickard (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Nitrogen and phosphorus nutrition and stoichiometry in the response of maize to various N rates under different rotation systems - B. L. Ma; Z. M. Zheng; M. J. Morrison; E. G. Gregorich (Nutrient Cycling in Agroecosystems, 2016)

Microbial diversity on intravascular catheters from paediatric patients - L. Zhang; N. Marsh; D. Long; M. Wei; M. Morrison; C. M. Rickard (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Nine microsatellite loci developed from the octocoral, Paragorgia arborea - D. K. Coykendall; C. L. Morrison (Conservation Genetics Resources, 2015)

Development of twelve microsatellite loci in the red tree corals Primnoa resedaeformis and Primnoa pacifica - C. L. Morrison; M. J. Springmann; K. M. Shroades; R. P. Stone (Conservation Genetics Resources, 2015)

Development and characterization of polymorphic microsatellite markers for the crested caracara, Caracara cheriway - Erin E. Vaughn; James F. Dwyer; Joan L. Morrison; Melanie Culver (Conservation Genetics Resources, 2015)

Development of ten microsatellite loci in the invasive giant African land snail, Achatina (=Lissachatina) fulica Bowdich, 1822 - C. L. Morrison; M. J. Springmann; D. D. Iwanowicz; C. M. Wade (Conservation Genetics Resources, 2015)

Design Control for Clinical Translation of 3D Printed Modular Scaffolds - Scott J. Hollister; Colleen L. Flanagan; David A. Zopf; Robert J. Morrison; Hassan Nasser; Janki J. Patel; Edward Ebramzadeh; Sophia N. Sangiorgio; Matthew B. Wheeler; Glenn E. Green (Annals of Biomedical Engineering, 2015)

Dichloroacetate affects proliferation but not survival of human colorectal cancer cells - L. M. Delaney; N. Ho; J. Morrison; N. R. Farias; D. D. Mosser; B. L. Coomber (Apoptosis, 2015)

Acute survivorship of the deep-sea coral Lophelia pertusa from the Gulf of Mexico under acidification, warming, and deoxygenation - Jay J. Lunden; Conall G. McNicholl; Christopher R. Sears; Cheryl L. Morrison; Erik E. Cordes (Frontiers in Marine Science, 2014)

Using a Gas-Phase Tracer Test to Characterize the Impact of Landfill Gas Generation on Advective-Dispersive Transport of VOCs in the Vadose Zone - Gregg R. Monger; Candice Morrison Duncan; Mark L. Brusseau (Water, Air, & Soil Pollution, 2014)

Development of eighteen microsatellite loci in walleye (Sander vitreus) - D. K. Coykendall; C. L. Morrison; W. Stott; M. J. Springmann (Conservation Genetics Resources, 2014)

Overexpression of α2,3sialyl T-antigen in breast cancer determined by miniaturized glycosyltransferase assays and confirmed using tissue microarray immunohistochemical analysis - Shilpa A. Patil; Wiam Bshara; Carl Morrison; E. V. Chandrasekaran; Khushi L. Matta; Sriram Neelamegham (Glycoconjugate Journal, 2014)

Determination of Chlorinated Solvent Sorption by Porous Material—Application to Trichloroethene Vapor on Cement Mortar - Marion Musielak; Mark L. Brusseau; Manuel Marcoux; Candice Morrison; Michel Quintard (Transport in Porous Media, 2014)

The ants of remote Polynesia revisited - L. W. Morrison (Insectes Sociaux, 2014)

Molecular investigation of bacterial communities on intravascular catheters: no longer just Staphylococcus - L. Zhang; J. Gowardman; M. Morrison; L. Krause; E. G. Playford; C. M. Rickard (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Changes in extreme temperature and precipitation in the Caribbean region, 1961–2010 - Tannecia S. Stephenson; Lucie A. Vincent; Theodore Allen; Cedric J. Van Meerbeeck; Natalie McLean; Thomas C. Peterson; Michael A. Taylor; Arlene P. Aaron‐Morrison; Thomas Auguste; Didier Bernard; Joffrey R. I. Boekhoudt; Rosalind C. Blenman; et al. (International Journal of Climatology, 2014)

Dynamic Contrast-Enhanced MRI Evaluation of Cerebral Cavernous Malformations - Blaine L. Hart; Saeid Taheri; Gary A. Rosenberg; Leslie A. Morrison (Translational Stroke Research, 2013)

Sensory and Physicochemical Properties of Smoked Catfish Sausages - Sovann Kin; Rebecca Morrison; Ana Claudia Tolentino; Alessandra J. Pham; Brian S. Smith; Taejo Kim; Juan L. Silva; M. Wes Schilling (Journal of Aquatic Food Product Technology, 2013)

Molecular investigation of bacterial communities on the inner and outer surfaces of peripheral venous catheters - L. Zhang; M. Morrison; G. R. Nimmo; K. S. Sriprakash; S. Mondot; J. R. Gowardman; N. George; N. Marsh; C. M. Rickard (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Polymorphic microsatellite markers developed from 454 pyro-sequencing in the cold water coral-associated squat lobster species, Eumunida picta (Chirostylidae: Eumunididae) - D. K. Coykendall; C. L. Morrison (Conservation Genetics Resources, 2013)

Changes in postural sway as a function of prolonged walking - Kathleen S. Thomas; Bonnie L. VanLunen; Steven Morrison (European Journal of Applied Physiology, 2013)

Population stratification may bias analysis of PGC-1α as a modifier of age at Huntington disease motor onset - Eliana Marisa Ramos; Jeanne C. Latourelle; Ji-Hyun Lee; Tammy Gillis; Jayalakshmi S. Mysore; Ferdinando Squitieri; Alba Di Pardo; Stefano Di Donato; Michael R. Hayden; Patrick J. Morrison; Martha Nance; Christopher A. Ross; et al. (Human Genetics, 2012)

The carbon footprint of maize production as affected by nitrogen fertilizer and maize-legume rotations - B. L. Ma; B. C. Liang; Dilip K. Biswas; Malcolm J. Morrison; Neil B. McLaughlin (Nutrient Cycling in Agroecosystems, 2012)

Acinetobacter , Aeromonas and Trichococcus populations dominate the microbial community within urban sewer infrastructure - J. L. VandeWalle; G. W. Goetz; S. M. Huse; H. G. Morrison; M. L. Sogin; R. G. Hoffmann; K. Yan; S. L. McLellan (Environmental Microbiology, 2012)
Summary We evaluated the population structure and temporal dynamics of the dominant community members within sewage influent from two wastewater treatment plants (WWTPs) in Milwaukee, WI. We generated > 1.1 M bacterial pyrotag sequences from the V6 hypervariable region of 16S rRNA genes from 38 influent samples and two samples taken upstream in the sanitary sewer system. Only a small fraction of pyrotags from influent samples (∼ 15%) matched sequences from human faecal samples. The faecal components of the sewage samples included enriched pyrotag populations from Lactococcus and Enterobacteriaceae relative to their fractional representation in human faecal samples. In contrast to the large number of distinct pyrotags that represent faecal bacteria such as Lachnospiraceae and Bacteroides , only one or two unique V6 sequences represented Acinetobacter , Aeromonas and Trichococcus , which collectively account for nearly 35% of the total sewage community. Two dominant Acinetobacter V6 pyrotags (designated Acineto tag 1 and Acineto tag 2) fluctuated inversely with a seasonal pattern over a 3‐year period, suggesting two distinct Acinetobacter populations respond differently to ecological forcings in the system. A single nucleotide change in the V6 pyrotags accounted for the difference in these populations and corresponded to two phylogenetically distinct clades based on full‐length sequences. Analysis of wavelet functions, derived from a mathematical model of temporal fluctuations, demonstrated that other abundant sewer associated populations including Trichococcus and Aeromonas had temporal patterns similar to either Acineto tag 1 or Acineto tag 2. Populations with related temporal fluctuations were found to significantly correlate with the same WWTP variables (5‐day BOD, flow, ammonia, total phosphorous and suspended solids). These findings illustrate that small differences in V6 sequences can represent phylogenetically and ecologically distinct taxa. This work provides insight into microbial community composition and dynamics within the defined environment of urban sewer infrastructure.

Exposed or not exposed? Exploring exposure classification in studies using administrative data to investigate outcomes following medication use during pregnancy - Luke E. Grzeskowiak; Andrew L. Gilbert; Janna L. Morrison (European Journal of Clinical Pharmacology, 2012)

Erratum to: Viscoelastic Properties of the Rat Brain in the Sagittal Plane: Effects of Anatomical Structure and Age - John D. Finan; Benjamin S. Elkin; Erica M. Pearson; Irene L. Kalbian; Barclay Morrison (Annals of Biomedical Engineering, 2012)

Viscoelastic Properties of the Rat Brain in the Sagittal Plane: Effects of Anatomical Structure and Age - John D. Finan; Benjamin S. Elkin; Erica M. Pearson; Irene L. Kalbian; Barclay Morrison (Annals of Biomedical Engineering, 2012)

Adapting to climate change through local municipal planning: barriers and challenges - Thomas G. Measham; Benjamin L. Preston; Timothy F. Smith; Cassandra Brooke; Russell Gorddard; Geoff Withycombe; Craig Morrison (Mitigation and Adaptation Strategies for Global Change, 2011)

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

Similarity in the dynamics of contralateral motor overflow through increasing frequency of movement in a single limb - S. Morrison; S. L. Hong; K. M. Newell (Experimental Brain Research, 2011)

Genetic discontinuity among regional populations of Lophelia pertusa in the North Atlantic Ocean - Cheryl L. Morrison; Steve W. Ross; Martha S. Nizinski; Sandra Brooke; Johanna Järnegren; Rhian G. Waller; Robin L. Johnson; Tim L. King (Conservation Genetics, 2011)

Abundance and distribution of major groups of diazotrophic cyanobacteria and their potential contribution to N 2 fixation in the tropical Atlantic Ocean - Nicole L. Goebel; Kendra A. Turk; Katherine M. Achilles; Ryan Paerl; Ian Hewson; Amanda E. Morrison; Joseph P. Montoya; Christopher A. Edwards; Jonathan P. Zehr (Environmental Microbiology, 2010)
Summary The abundances of six N 2 ‐fixing cyanobacterial phylotypes were profiled at 22 stations across the tropical Atlantic Ocean during June 2006, and used to model the contribution of the diazotrophs to N 2 fixation. Diazotroph abundances were measured by targeting the nifH gene of Trichodesmium , unicellular groups A, B, C (UCYN‐A, UCYN‐B and UCYN‐C), and diatom‐cyanobiont symbioses Hemiaulus–Richelia , Rhizosolenia–Richelia and Chaetoceros–Calothrix . West to east gradients in temperature, salinity and nutrients [NO 3 ‐ + NO 2 ‐ , PO 4 3− , Si(OH) 4 ] showed the influence of the Amazon River plume and its effect on the distributions of the diazotrophs. Trichodesmium accounted for more than 93% of all nifH genes detected, dominated the warmer waters of the western Atlantic, and was the only diazotroph detected at the equatorial upwelling station. UCYN‐A was the next most abundant (> 5% of all nifH genes) and dominated the cooler waters of the eastern Atlantic near the Cape Verde Islands. UCYN‐C was found at a single depth (200 m) of high salinity and low temperature and nutrients, whereas UCYN‐B cells were widespread but in very low abundance (6.1 × 10 1 ± 4.6 × 10 2 gene copies l −1 ). The diatom‐cyanobionts were observed primarily in the western Atlantic within or near the high Si(OH) 4 input of the Amazon River plume. Overall, highest diazotroph abundances were observed at the surface and declined with depth, except for some subsurface peaks in Trichodesmium , UCYN‐B and UCYN‐A. Modelled contributions of Trichodesmium , UCYN‐B and UCYN‐A to total N 2 fixation suggested that Trichodesmium had the largest input, except for the potential of UCYN‐A at the Cape Verde Islands.

Ironing out the wrinkles in the rare biosphere through improved OTU clustering - Susan M. Huse; David Mark Welch; Hilary G. Morrison; Mitchell L. Sogin (Environmental Microbiology, 2010)
Summary Deep sequencing of PCR amplicon libraries facilitates the detection of low‐abundance populations in environmental DNA surveys of complex microbial communities. At the same time, deep sequencing can lead to overestimates of microbial diversity through the generation of low‐frequency, error‐prone reads. Even with sequencing error rates below 0.005 per nucleotide position, the common method of generating operational taxonomic units (OTUs) by multiple sequence alignment and complete‐linkage clustering significantly increases the number of predicted OTUs and inflates richness estimates. We show that a 2% single‐linkage preclustering methodology followed by an average‐linkage clustering based on pairwise alignments more accurately predicts expected OTUs in both single and pooled template preparations of known taxonomic composition. This new clustering method can reduce the OTU richness in environmental samples by as much as 30–60% but does not reduce the fraction of OTUs in long‐tailed rank abundance curves that defines the rare biosphere.

Nitrous oxide fluxes from corn fields: on‐farm assessment of the amount and timing of nitrogen fertilizer - B. L. MA; T. Y. WU; N. TREMBLAY; W. DEEN; M. J. MORRISON; N. B. MCLAUGHLIN; E. G. GREGORICH; G. STEWART (Global Change Biology, 2010)
Nitrogen fertilization is considered as an important source of atmospheric N 2 O emission. A seven site‐year on‐farm field experiment was conducted at Ottawa and Guelph, ON and Saint‐Valentin, QC, Canada to characterize the affect of the amount and timing of N fertilizer on N 2 O emission in corn ( Zea mays L.) production. Using the static chamber method, gas samples were collected for 28‐days after preplant and 28‐days after sidedress fertilization at the seven site‐year, resulting in 14 monitoring periods. For both methods of fertilization, peak N 2 O flux and cumulative emission increased with the amount of N applied, with rates ranging from 30 to 900 μg N m −2 h −1 . Depending on N amount and time of application, cumulative emission varied from 0.05 to 2.42 kg N ha −1 , equivalent to 0.03% to 1.45% of the N fertilizer applied. Differences in N 2 O emission peaks among fertilizer treatments were clearly separated in 13 out of 14 monitoring periods. Total N 2 O emissions may have been underestimated compared with annual monitoring in 10 out of the 49 cases because the monitoring period ended before N 2 O efflux returned to the baseline level. The flux of N 2 O was negligible when soil mineral N in the 0–15 cm layer was −1 . While rainfall stimulated emission, soil temperature > 15 °C was likely the driving force responsible for the higher levels of N 2 O found for sidedress than preplant application methods. However, caution must be taken when interpreting these later results as preplant fertilization may have continuously stimulated N 2 O emissions after the 28‐days monitoring period, especially in situations where N 2 O effluxes have not fallen back to their baseline levels. Increasing fertilizer rates from 90 to 150 kg N ha −1 resulted in slight increases in yields, but doubled cumulative N 2 O emissions.

Patient preferences and National Health Service costs: a cost-consequences analysis of cancer genetic services - Gethin L. Griffith; Rhiannon Tudor Edwards; J. Mark G. Williams; Jonathon Gray; Val Morrison; Clare Wilkinson; Jim Turner; Barbara France; Paul Bennett (Familial Cancer, 2009)

Nutrient Pollution in Laucala Bay, Fiji Islands - Sarabjeet Singh; W. G. L. Aalbersberg; R. J. Morrison (Water, Air, & Soil Pollution, 2009)

Addition of individual chromosomes of maize inbreds B73 and Mo17 to oat cultivars Starter and Sun II: maize chromosome retention, transmission, and plant phenotype - Howard W. Rines; Ronald L. Phillips; Ralf G. Kynast; Ron J. Okagaki; Mark W. Galatowitsch; Paul A. Huettl; Adrian O. Stec; Morrison S. Jacobs; Jayanti Suresh; Hedera L. Porter; Matthew D. Walch; Candida B. Cabral (Theoretical and Applied Genetics, 2009)

Paliperidone suppresses the development of the aggressive phenotype in a developmentally sensitive animal model of escalated aggression - Jared J. Schwartzer; Randall L. Morrison; Lesley A. Ricci; Richard H. Melloni (Psychopharmacology, 2009)

Effect of PCR amplicon size on assessments of clone library microbial diversity and community structure - Julie A. Huber; Hilary G. Morrison; Susan M. Huse; Phillip R. Neal; Mitchell L. Sogin; David B. Mark Welch (Environmental Microbiology, 2009)
Summary PCR‐based surveys of microbial communities commonly use regions of the small‐subunit ribosomal RNA (SSU rRNA) gene to determine taxonomic membership and estimate total diversity. Here we show that the length of the target amplicon has a significant effect on assessments of microbial richness and community membership. Using operational taxonomic unit (OTU)‐ and taxonomy‐based tools, we compared the V6 hypervariable region of the bacterial SSU rRNA gene of three amplicon libraries of c. 100, 400 and 1000 base pairs (bp) from each of two hydrothermal vent fluid samples. We found that the smallest amplicon libraries contained more unique sequences, higher diversity estimates and a different community structure than the other two libraries from each sample. We hypothesize that a combination of polymerase dissociation, cloning bias and mispriming due to secondary structure accounts for the differences. While this relationship is not linear, it is clear that the smallest amplicon libraries contained more different types of sequences, and accordingly, more diverse members of the community. Because divergent and lower abundant taxa can be more readily detected with smaller amplicons, they may provide better assessments of total community diversity and taxonomic membership than longer amplicons in molecular studies of microbial communities.

Quantifying Eradication Success: the Removal of Feral Pigs from Santa Cruz Island, California - DAVID S. L. RAMSEY; JOHN PARKES; SCOTT A. MORRISON (Conservation Biology, 2009)
A major challenge facing pest‐eradication efforts is determining when eradication has been achieved. When the pest can no longer be detected, managers have to decide whether the pest has actually been eliminated and hence to decide when to terminate the eradication program. For most eradication programs, this decision entails considerable risk and is the largest single issue facing managers of such programs. We addressed this issue for an eradication program of feral pigs ( Sus scrofa ) from Santa Cruz Island, California. Using a Bayesian approach, we estimated the degree of confidence in the success of the eradication program at the point when monitoring failed to detect any more pigs. Catch‐effort modeling of the hunting effort required to dispatch pigs during the eradication program was used to determine the relationship between detection probability and searching effort for different hunting methods. We then used these relationships to estimate the amount of monitoring effort required to declare eradication successful with criteria that either set a threshold for the probability that pigs remained undetected (type I error) or minimized the net expected costs of the eradication program (cost of type I and II errors). For aerial and ground‐based monitoring techniques, the amount of search effort required to declare eradication successful on the basis of either criterion was highly dependent on the prior belief in the success of the program unless monitoring intensities exceeded 30 km of searching effort per square kilometer of search area for aerial monitoring and, equivalently, 38 km for ground monitoring. Calculation of these criteria to gauge the success of eradication should form an essential component of any eradication program as it allows for a transparent assessment of the risks inherent in the decision to terminate the program.

Expanding the Global Network of Protected Areas to Save the Imperiled Mediterranean Biome - EMMA C. UNDERWOOD; KIRK R. KLAUSMEYER; ROBIN L. COX; SYLVIA M. BUSBY; SCOTT A. MORRISON; M. REBECCA SHAW (Conservation Biology, 2009)
Global goals established by the Convention on Biological Diversity stipulate that 10% of the world's ecological regions must be effectively conserved by 2010. To meet that goal for the mediterranean biome, at least 5% more land must be formally protected over the next few years. Although global assessments identify the mediterranean biome as a priority, without biologically meaningful analysis units, finer‐resolution data, and corresponding prioritization analysis, future conservation investments could lead to more area being protected without increasing the representation of unique mediterranean ecosystems. We used standardized analysis units and six potential natural vegetation types stratified by 3 elevation zones in a global gap analysis that systematically explored conservation priorities across the mediterranean biome. The highest levels of protection were in Australia, South Africa, and California‐Baja California (from 9–11%), and the lowest levels of protection were in Chile and the mediterranean Basin ( 30% conversion and suggest that these assemblages be elevated to high‐priority status in future conservation efforts.

Detection of meticillin-resistant Staphylococcus aureus and Panton-Valentine leukocidin directly from clinical samples and the development of a multiplex assay using real-time polymerase chain reaction - L. Renwick; A. Hardie; E. K. Girvan; M. Smith; G. Leadbetter; E. Claas; D. Morrison; A. P. Gibb; J. Dave; K. E. Templeton (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Probing the role of copper in the biosynthesis of the molybdenum cofactor in Escherichia coli and Rhodobacter sphaeroides - M. Scott Morrison; Paul A. Cobine; Eric L. Hegg (JBIC Journal of Biological Inorganic Chemistry, 2007)

Inverse relations in the patterns of muscle and center of pressure dynamics during standing still and movement postures - S. Morrison; S. L. Hong; K. M. Newell (Experimental Brain Research, 2007)

Multicenter retrospective development and validation of a clinical prediction rule for nosocomial invasive candidiasis in the intensive care setting - L. Ostrosky-Zeichner; C. Sable; J. Sobel; B. D. Alexander; G. Donowitz; V. Kan; C. A. Kauffman; D. Kett; R. A. Larsen; V. Morrison; M. Nucci; P. G. Pappas; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

Comprehensive genetic analyses reveal evolutionary distinction of a mouse ( Zapus hudsonius preblei ) proposed for delisting from the US Endangered Species Act - TIM L. KING; JOHN F. SWITZER; CHERYL L. MORRISON; MICHAEL S. EACKLES; COLLEEN C. YOUNG; BARBARA A. LUBINSKI; PAUL CRYAN (Molecular Ecology, 2006)
Zapus hudsonius preblei , listed as threatened under the US Endangered Species Act (ESA), is one of 12 recognized subspecies of meadow jumping mice found in North America. Recent morphometric and phylogenetic comparisons among Z. h. preblei and neighbouring conspecifics questioned the taxonomic status of selected subspecies, resulting in a proposal to delist the Z. h. preblei from the ESA. We present additional analyses of the phylogeographic structure within Z. hudsonius that calls into question previously published data (and conclusions) and confirms the original taxonomic designations. A survey of 21 microsatellite DNA loci and 1380 base pairs from two mitochondrial DNA (mtDNA) regions (control region and cytochrome b ) revealed that each Z. hudsonius subspecies is genetically distinct. These data do not support the null hypothesis of a homogeneous gene pool among the five subspecies found within the southwestern portion of the species’ range. The magnitude of the observed differentiation was considerable and supported by significant findings for nearly every statistical comparison made, regardless of the genome or the taxa under consideration. Structuring of nuclear multilocus genotypes and subspecies‐specific mtDNA haplotypes corresponded directly with the disjunct distributions of the subspecies investigated. Given the level of correspondence between the observed genetic population structure and previously proposed taxonomic classification of subspecies (based on the geographic separation and surveys of morphological variation), we conclude that the nominal subspecies surveyed in this study do not warrant synonymy, as has been proposed for Z. h. preblei , Z. h. campestris , and Z. h. intermedius .

Phylogeographic Analyses Suggest Multiple Lineages of Crystallaria asprella (Percidae: Etheostominae) - Cheryl L. Morrison; David P. Lemarié; Robert M. Wood; Tim L. King (Conservation Genetics, 2006)

The effects of unilateral muscle fatigue on bilateral physiological tremor - S. Morrison; J. Kavanagh; S. J. Obst; J. Irwin; L. J. Haseler (Experimental Brain Research, 2005)

An Assessment of Turbulence Profiles in Rural and Urban Environments Using Local Measurements and Numerical Weather Prediction Results - N. L. Morrison; H. N. Webster (Boundary-Layer Meteorology, 2005)

MUSCLE-DERIVED CD45−SCA-1+C-KIT− PROGENITOR CELLS GIVE RISE TO SKELETAL MUSCLE MYOTUBES IN VITRO - CASSANDRE L. ROYER; JONATHAN C. HOWELL; PAUL R. MORRISON; EDWARD F. SROUR; MERVIN C. YODER (In Vitro Cellular & Developmental Biology - Animal, 2002)

Conservation Value of Private Lands for Crested Caracaras in Florida - Joan L. Morrison; Stephen R. Humphrey (Conservation Biology, 2001)
In southcentral Florida, where agricultural lands are being converted rapidly to urban development, much of the remaining nonurban habitat occurs on privately owned cattle ranches. We studied the Crested Caracara ( Caracara cheriway ), a threatened bird of prey, to learn the role of private lands in sustaining the population. We investigated patterns of distribution and reproductive activity of breeding pairs of caracaras in relation to patterns of land ownership and use. Eighty‐two percent of 73 active nest sites found were on privately owned cattle ranches. We rarely found breeding pairs on publicly owned lands, most of which are managed as natural areas (no agricultural production and limited livestock grazing) to support native plant and animal communities. In 46 breeding areas with 4 years of known histories of occupancy and reproduction, pairs nesting on lands where the major land use was cattle ranching exhibited higher rates of breeding‐area occupancy, attempted breeding during more years, initiated egg laying earlier, exhibited higher nesting success, and attempted a second brood after successfully fledging a first brood more often than pairs nesting on lands managed as natural areas. Compositional analysis suggested nonrandom selection of habitats by breeding pairs of caracaras in their establishment of a home range in the current landscape of southcentral Florida. Compared with random areas and available habitat in the overall study area, caracara home ranges had higher proportions of improved pasture and lower proportions of forest, woodland, oak scrub, and marsh. Which management activities favor and do not favor caracaras is uncertain, and hypotheses should be formulated and tested to guide future conservation applications. Particular grazing and fire management practices on privately and publicly owned lands may affect the structure of vegetation and prey communities in ways that influence caracaras. Or, replacement of native by exotic grasses may retain structurally suitable plant communities, whereas fertilization and grazing may increase productivity and nutrient cycling in ways that favor caracaras. Given continued conversion of natural habitats and agricultural lands to urban development, it is important to recognize that cattle ranches may provide important resources for wildlife conservation. Although cattle ranching is not likely to benefit all species historically associated with the native prairie ecosystem in Florida, finding ways to retain this land use may be important for the conservation of Florida's population of Crested Caracaras and other organisms of Florida's dry prairies.

Patterns of Predation Risk and Survival of Bird Nests in a Chilean Agricultural Landscape - Mary F. Willson; Joan L. Morrison; Kathryn E. Sieving; Toni L. De Santo; Leonard Santisteban; Iván Díaz (Conservation Biology, 2001)
We used experimental nests baited with California Quail ( Callipepla californica ) eggs or clay eggs to examine relative risks of nest predation in an agricultural landscape and in two large forest preserves in a south‐temperate rainforest in Chile. The most common predators, as identified by marks on clay eggs, were a caracara ( Milvago chimango ), a blackbird ( Curaeus curaeus ), and rodents. Nest losses from predation were similar in large and small forest patches and lower in patches than in extensive forest. In general, predation risk was higher (and nest survival therefore lower) on forest edges than in forest interior, in short‐grass pasture than in tall‐grass pasture, in narrow corridors than in wide corridors, and on visible nests than on concealed nests. High predation risks in pasture habitat tended to increase the risk of nest predation in adjacent forest edges. For open‐cup nesters, the risk of nest predation was relatively high in the present agricultural landscape, indicating that much of the available wooded habitat ( forest edges, narrow corridors) offers poor nesting habitat, although it may be suitable for foraging and traveling. The numerous bird‐plant mutualisms in this landscape may be at risk if nesting success of the principal mutualists is consistently low.

Facilitating Development of Multiple-Species Conservation Reserves and Habitat Conservation Plans: A Synthesis of Recommendations - MICHAEL L. MORRISON (Environmental Management, 2000)

The Impact of Logging on Wildlife: A Study in Northeastern Pennsylvania - Todd S. Fredericksen; Brad D. Ross; Wayne Hoffman; Eric Ross; Michael L. Morrison; Jan Beyea; Michael B. Lester; Bradley N. Johnson (Journal of Forestry, 2000)
Seeing and conserving wildlife are among the most important management objectives for nonindustrial private landowners in the eastern United States. Landowners want profitable timber harvests but also want to know how harvesting will affect their wildlife. The study examined associations between stand characteristics and wildlife abundance on 40 stands receiving different logging intensities in northeastern Pennsylvania and found that landowners have some choices when harvesting their stands for retaining or attracting different types of wildlife.

Transport Across the Primate Blood-Brain Barrier of a Genetically Engineered Chimeric Monoclonal Antibody to the Human Insulin Receptor - M. Josephina Coloma; Hwa Jeong Lee; Atsushi Kurihara; Elliot M. Landaw; Ruben J. Boado; Sherie L. Morrison; William M. Pardridge (Pharmaceutical Research, 2000)

Relative Abundance and Species Richness of Herpetofauna in Forest Stands in Pennsylvania - Brad Ross; Todd Fredericksen; Eric Ross; Wayne Hoffman; Michael L. Morrison; Jan Beyea; Michael B. Lester; Bradley N. Johnson; Nell J. Fredericksen (Forest Science, 2000)
The relative abundance and species richness of herpetofauna was investigated to assess the impact of recent logging operations in 47 forest stands in northeastern Pennsylvania during 1996 and 1997. Stands including nonindustrial private forestlands and public lands that have received some type of harvesting within the last 8 yr ranged from near complete overstory tree cover to complete removal of overstory cover. Stands included the two dominant forest types in the region: northern hardwood (Betula, Fagus, Prunus, Acer, and Tsuga spp.) and oak-hickory/(Quercus and Carya spp.). A total of 8,181 individuals of 26 species (12 salamander, 7 snake, 6 frog, and 1 toad species) were observed in the study stands. The relative abundance and species richness of salamanders increased significantly with increasing retention of tree basal area. Forest stands containing > 15 m²/ha live tree basal area appeared to be a threshold level for high salamander abundance. Snake species abundance and richness increased significantly with increasing removal of tree basal area. The abundance of anuran species showed no significant relationship with amount of tree basal area removal, but the relative abundance and species richness of anurans depended on the presence of water within or bordering the stands. Forest type did not change the overall response of herpetofauna community composition to forest harvesting, although salamanders were more abundant in northern hardwood stands, and snakes were more abundant in oak-hickory stands. Patterns and threshold levels of abundance and species richness of herpetofauna determined in this study may be used to maintain the abundance and richness of selected species when harvesting forest stands. For. Sci. 46(1):139-146.

β3-Adrenergic receptor Trp64Arg polymorphism does not predict incident CHD or carotid intima-media thickness in a community-based sample of whites: the ARIC study - A.C. Morrison; F.L. Brancati; A.R. Folsom; L. Smith; E. Boerwinkle (Human Genetics, 1999)

β3-Adrenergic receptor Trp64Arg polymorphism does not predict incident CHD or carotid intima-media thickness in a community-based sample of whites: the ARIC study - A.C. Morrison; F.L. Brancati; A.R. Folsom; L. Smith; E. Boerwinkle (Human Genetics, 1999)

Genetic and Environmental Controls on the Establishment of the Invasive Grass, Phalaris arundinacea - Jane Molofsky; Shannon L. Morrison; Charles J. Goodnight (Biological Invasions, 1999)

Litter decomposition rates in Canadian forests - T. R. Moore; J. A. Trofymow; B. Taylor; C. Prescott; C. Camiré; L. Duschene; J. Fyles; L. Kozak; M. Kranabetter; I. Morrison; M. Siltanen; S. Smith; et al. (Global Change Biology, 1999)
The effect of litter quality and climate on the rate of decomposition of plant tissues was examined by the measurement of mass remaining after 3 years’ exposure of 11 litter types placed at 18 forest sites across Canada. Amongst sites, mass remaining was strongly related to mean annual temperature and precipitation and amongst litter types the ratio of Klason lignin to nitrogen in the initial tissue was the most important litter quality variable. When combined into a multiple regression, mean annual temperature, mean annual precipitation and Klason lignin:nitrogen ratio explained 73% of the variance in mass remaining for all sites and tissues. Using three doubled CO 2 GCM climate change scenarios for four Canadian regions, these relationships were used to predict increases in decomposition rate of 4–7% of contemporary rates (based on mass remaining after 3 years), because of increased temperature and precipitation. This increase may be partially offset by evidence that plants growing under elevated atmospheric CO 2 concentrations produce litter with high lignin:nitrogen ratios which slows the rate of decomposition, but this change will be small compared to the increased rate of decomposition derived from climatic changes.

Animal Burrowing Attributes Affecting Hazardous Waste Management - K. SHAWN SMALLWOOD; MICHAEL L. MORRISON; JAN BEYEA (Environmental Management, 1998)

Development and Evaluation of Habitat Models for Herpetofauna and Small Mammals - William M. Block; Michael L. Morrison; Peter E. Scott (Forest Science, 1998)
We evaluated the ability of discriminant analysis (DA), logistic regression (LR), and multiple regression (MR) to describe habitat use by amphibians, reptiles, and small mammals found in California oak woodlands. We also compared models derived from pitfall and live trapping data for several species. Habitat relations modeled by DA and LR produced similar results, averaging about 70% classification success of the trapping stations to the correct group (capture or noncapture habitat). Although more variables were included in DA (4-5) than in LR (2-3), those included in LR were typically a subset of those in DA. On average, MR habitat models accounted for 56% of the variation in the index of relative species' abundance. The variables included in the MR models were seldom the same as those for DA and LR. Most differences between MR and the other two methods were related to differences in spatial scale: MR modeled habitat among grids, whereas DA and LR modeled habitat within grids. Habitat models for the same species differed between the trapping methods used. Live traps are most useful for describing general habitat relations of some small mammal species across large geographic areas, whereas pitfall traps are useful for intensive sampling of a larger portion of the vertebrate community within smaller geographic areas. Thus, the choice of trapping methods must be based on the study goals, biology of the species, and the spatial scale of study. For. Sci. 44(3):430-437.

Fish communities in a diked Lake Erie wetland and an adjacent undiked area - David L. Johnson; William E. Lynch; Todd W. Morrison (Wetlands, 1997)

Biological and pharmacokinetic properties of a novel immunoglobulin-CD4 fusion protein - J. B. Lyczak; S. L. Morrison (Archives of Virology, 1994)

An immunological study of infection of hamsters with large and small plaque canine distemper viruses - S. L. Cosby; J. Morrison; B. K. Rima; S. J. Martin (Archives of Virology, 1983)

Evaluation of the mutagenic potential of bacterial polychlorinated biphenyl biodegradation products - G. S. Sayler; M. C. Reid; B. K. Perkins; R. M. Pagni; R. L. Smith; T. K. Rao; J. L. Epler; W. D. Morrison; R. DuFrain (Archives of Environmental Contamination and Toxicology, 1982)

The changing role of soil pests attacking potato tubers - H. E. Morrison; L. G. Gentner; R. F. Koontz; R. W. Every (American Journal of Potato Research, 1967)